Method for preparing CHA-AFT zeolite intergrowth COE-10 and its use in heterogeneous catalysis
By synthesizing quartz materials with CHA type and AFT type framework structures and optimizing their structure through steam treatment, the problem of insufficient catalyst performance in the prior art is solved, and excellent catalytic effect and time stability in the methanol to olefin conversion process are achieved.
Patent Information
- Application Number
- JP2021568271
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-15
- Filing Date
- 2020-05-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-05-14
AI Technical Summary
It is difficult to synthesize heterogeneous catalysts with novel and improved properties in the prior art, especially in the methanol to olefin conversion (MTO) process, where the catalysts have insufficient stability and performance.
A quartz material with CHA type and AFT type skeleton structures is synthesized by a method including the following steps: preparing a mixture of these materials, heating to form a quartz material with CHA type and AFT type skeleton structures, and removing part of the trivalent elements by steam treatment to form a quartz material with excellent catalytic properties.
The excellent catalytic performance of quartz materials in the methanol to olefin conversion (MTO) process is achieved, which extends the time stability of the process and improves the overall performance of the material.
Smart Images

Figure 0007648541000013 
Figure 0007648541000014 
Figure 0007648541000015
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for the preparation of a zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure, in particular COE-10, as well as to a method for the preparation of a synthetic zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure, in particular COE-10, obtainable by the method of the present invention.Furthermore, the present invention relates to a synthetic zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolitic intergrowth phases of one or more zeolites having an AFT-type framework structure, in particular COE-10, as well as the use of such material as such or obtainable by the method of the present invention, in particular as a heterogeneous catalyst. [Background technology]
[0002] Molecular sieves have been classified by the Structure Commission of the International Zeolite Association according to the rules of the IUPAC Commission on the Nomenclature of Zeolites, in which framework zeolites and other crystalline microporous molecular sieves whose structures have been established are assigned three-letter codes and are described in the Atlas of Zeolite Framework Types, 5th ed., Elsevier, London, England (2001).
[0003] Among said zeolitic materials, Chabazite is a well-studied example and is a classical representative of the class of zeolitic materials with CHA framework structure. Besides aluminosilicates such as Chabazite, the class of zeolitic materials with CHA framework structure includes a large number of compounds that further contain phosphorus in the framework structure, and are therefore known to be called silicoaluminophosphates (SAPO). In addition to said compounds, further molecular sieves of CHA structure type are known to contain aluminum and phosphorus in the framework structure, but little or no silica, and are therefore called aluminophosphates (APO). Zeolitic materials belonging to the class of molecular sieves with CHA framework structure are used in various applications, in particular to act as heterogeneous catalysts in a wide range of reactions, such as methanol to olefins catalytic reaction and selective catalytic reduction of nitrogen oxides NOx, to name just two of the most important applications. Zeolitic materials of the CHA framework type are characterized by a system of double six-membered rings (D6R) and three-dimensional eight-membered ring (8MR) pores / channels containing cages.
[0004] Among the methods for synthesizing zeolites with a CHA-type framework structure, WO2013 / 068976A1 relates to an organic template-free synthesis method for producing zeolitic materials with a CHA-type framework structure.
[0005] US2012 / 0189518A1 discloses a NOx inhibitor having one or more transition metals selected from the list including iron and copper. x In the present application, the molecular sieve has at least one intergrowth phase of at least two different pore three-dimensional framework structures. The preferred intergrowth phases disclosed in the document are selected from the group consisting of AEI, GME, AFX, AFT and LEV, with CHA as the second framework structure of each intergrowth phase, where the intergrowth phase between AEI and CHA is particularly preferred. However, the material taught in US2012 / 0189518A1 is a silicoaluminophosphate.
[0006] Similarly, US6334994B1, WO98 / 15496A1, and WO02 / 070407A1 relate to silicoaluminophate intergrowths of AEI and CHA, said materials being used as heterogeneous catalysts in the conversion of methanol to olefins.
[0007] On the other hand, WO2019 / 024909A1 relates to the synthesis of zeolitic materials containing transition metals and one or more of potassium and cesium, and their use as catalysts in the selective catalytic reduction of nitrogen oxides using ammonia as the reducing agent.
[0008] Bhadra, BN et al., Journal of Catalysis 2018, 365, pp. 94-104, relates to the conversion of ethylene to propylene over SSZ-13 prepared without an organic structure directing agent that is subsequently steamed. More specifically, the paper discusses steaming such materials, including SSZ-13 prepared from the interzeolitic conversion of zeolite Y in the presence of potassium ions. The latter material is described as being less stable and exhibiting significantly inferior performance in the conversion of ethylene to propylene compared to SSZ-13 prepared from a mixture containing seeds and without potassium ions.
[0009] GWSkeels et al., in Microporous and Mesoporous Materials, disclose a study on a zeolite described as a chabazite topology with faults along the c direction, which is the stacking direction of the ABC double hexagonal (D6R) material. The zeolite is designated LZ-276 and can be prepared by crystallizing the zeolite from a synthesis gel at 125°C.
[0010] EP3167953A1 discloses the hydrothermal synthesis of zeolite membranes having a CHA crystal structure using an aqueous reaction mixture, in which a non-dealuminized FAU zeolite is used as a source of Si and Al elements.
[0011] S. Goel et al. have reported a study on the synthesis of zeolites by interzeolite conversion without the use of organic structure directing agents, which resulted in the synthesis of high-silica MFI, CHA, STF and MTW zeolites from FAU or BEA matrices.
[0012] Y. Ji et al. disclosed a study on the organic-free synthesis of CHA-type zeolite catalyst for methanol-to-olefins reaction, whereby CHA-type zeolite was prepared from hydrothermal conversion of FAU-type zeolite and further dealuminated.
[0013] Y. Naraki et al. have disclosed new intergrowth zeolites with AFX / CHA structure. The intergrowth zeolites, called ZTS-1 and ZTS-2, were prepared using dual structure directing agents.
[0014] St. Wilson et al. disclose studies on the synthesis, properties and structure of SAPO-56, a member of the ABC double hexagonal ring family of materials with the stacking sequence AABBCCBB.
[0015] However, there remains a need for the synthesis of new zeolitic materials exhibiting new and improved properties, especially in the field of heterogeneous catalysis. Summary of the Invention [Problem to be solved by the invention]
[0016] The object of the present invention is therefore to provide a method for the synthesis of new zeolitic materials with new and improved properties, especially in the field of heterogeneous catalysis. It has therefore been surprisingly found that by steaming a particular zeolitic material with CHA-type framework structure obtained from an organic template-free synthesis, in particular a zeolitic material comprising one or more zeolitic intergrowth phases of zeolites with CHA-type framework structure and zeolites with AFT-type framework structure, in particular COE-10, a zeolitic material exhibiting excellent catalytic properties is obtained. In particular, it has been found quite unexpectedly that said material exhibits excellent results in heterogeneous catalysis, in particular in methanol to olefins (MTO), and surprisingly, the flow time of said material in the MTO process can be significantly extended after being subjected to a particular steaming treatment method. [Means for solving the problem]
[0017] The present invention therefore relates to a method for the preparation of a zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure comprising SiO2 and X2O3, and one or more zeolites having an AFT-type framework structure comprising SiO2 and X2O3, where X is a trivalent element, said method comprising: (1) preparing a mixture comprising one or more sources of SiO2, one or more sources of X2O3, and seed crystals comprising a zeolitic material, the zeolitic material comprising SiO2 and X2O3 in its framework structure and having a CHA-type framework structure; (2) heating the mixture prepared in (1) to obtain a zeolitic material comprising one or more zeolitic intergrowth phases with one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure; (R) subjecting the zeolitic material obtained in (2) to a treatment in order to remove at least a portion of the X's, preferably the tetrahedrally coordinated X's, from the framework structure of the zeolitic material; Includes.
[0018] Furthermore, the present invention relates to a synthetic zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure, the zeolitic material being obtainable and / or having been obtained by the method of any one of the embodiments disclosed herein.
[0019] The present invention further relates to a synthetic zeolitic material, preferably obtainable and / or obtained by the method of any one of the embodiments disclosed herein, comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure comprising SiO2 and X2O3 and one or more zeolites having an AFT-type framework structure comprising SiO2 and X2O3, wherein X is a trivalent element, and wherein the intergrowth phases are in the range of 3,000 to 3,800 cm at a pressure of 1,000 Pa. -1 In the CO FT-IR spectrum of zeolite materials measured in the wavenumber range, the absorption band with the highest negative absorbance is at 3,580–3,700 cm -1 , preferably 3,600 to 3,680 cm -1 , more preferably 3,620 to 3,670 cm -1 , more preferably 3,630 to 3,660 cm -1 , more preferably 3,640 to 3,650 cm -1 The absorbance band with the highest positive absorbance is 3,350–3,560 cm -1 , preferably 3,370 to 3,540 cm -1 , more preferably 3,390 to 3,520 cm -1 , more preferably 3,410 to 3,500 cm -1 , more preferably 3,430 to 3,480 cm -1 , more preferably 3,450 to 3,460 cm -1 Indicates the maximum value in a range.
[0020] Furthermore, the present invention is directed to the use of sieves as molecular sieves for ion exchange, as adsorbents, or as adsorbents for the removal of nitrogen oxides, NO xfor the selective catalytic reduction (SCR) of CO; for the storage and / or adsorption of CO; for the oxidation of NH, in particular the oxidation of NH slip in diesel systems; as catalysts and / or catalyst supports for the decomposition of NO, preferably as additives in fluid catalytic cracking (FCC) processes and / or as catalysts in organic conversion reactions, preferably the conversion of alcohols to olefins, more preferably in the conversion of methanol to olefins (MTO), more preferably the conversion of nitrogen oxides NO x For selective catalytic reduction (SCR) of nitrogen oxides NO in exhaust gases from an internal combustion engine, preferably a diesel engine or a lean-burn gasoline engine, x More preferably, the present invention relates to the use of the zeolitic material in alcohol to olefins conversion, more preferably the use of the zeolitic material in methanol to olefins (MTO) conversion catalyst.
[0021] The zeolitic material obtained in (2) comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure preferably comprises COE-10, more preferably the zeolitic material obtained in (2) is COE-10.
[0022] The zeolite material contained in the seed crystals may be prepared by any known method. The zeolite material contained in the seed crystals (1) is (A) preparing a mixture comprising one or more structure directing agents and a first zeolitic material comprising SiO2 and X2O3 in its framework structure, said first zeolitic material having a FAU-type framework structure, a FER-type framework structure, a TON-type framework structure, a MTT-type framework structure, a BEA-type framework structure, and / or a MFI-type framework structure, preferably a FAU-type framework structure; (B) heating the mixture obtained in (A) to obtain a second zeolitic material comprising SiO2 and X2O3 in its framework structure, said second zeolitic material having a CHA-type framework structure; It is preferred that the composition is obtained by a method comprising the steps of:
[0023] The first zeolitic material having an FAU-type framework structure preferably comprises one or more zeolites having an FAU-type framework structure, the one or more zeolites having an FAU-type framework structure being selected from the group consisting of Li-LSX, zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, SAPO-37, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof, more preferably from the group consisting of zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof, more preferably from the group consisting of zeolite X, zeolite Y, ZSM-20, ZSM-3, faujasite, and mixtures of two or more thereof, more preferably from the group consisting of zeolite X, zeolite Y, faujasite, and mixtures of two or more thereof. It is particularly preferred that the one or more zeolites having an FAU-type framework structure comprise zeolite X and / or zeolite Y, preferably zeolite Y, and more preferably the one or more zeolites having an FAU-type framework structure are zeolite X and / or zeolite Y, preferably zeolite Y.
[0024] It is preferred that the mixture prepared in (1) and heated in (2) is substantially free of organic template. Therefore, the method of the present invention disclosed herein is preferably carried out in the absence of organic template. It is particularly preferred that the mixture prepared in (1) and heated in (2) contains 1% by weight or less of organic template, preferably 0.5% by weight or less, more preferably 0.1% by weight or less, more preferably 0.05% by weight or less, more preferably 0.01% by weight or less, more preferably 0.005% by weight or less, more preferably 0.001% by weight or less of organic template, based on the total weight of the mixture.
[0025] It is preferred that the mixture prepared in (A) and heated in (B) is substantially free of phosphorus and / or phosphorus-containing compounds. Thus, the process for preparing the zeolitic material contained in the seed crystals in (1) is preferably carried out in the absence of phosphorus and / or phosphorus-containing compounds. It is particularly preferred that the mixture prepared in (1) and heated in (2) contains 1% by weight or less of phosphorus and / or phosphorus-containing compounds, preferably 0.5% by weight or less, more preferably 0.1% by weight or less, more preferably 0.05% by weight or less, more preferably 0.01% by weight or less, more preferably 0.005% by weight or less, more preferably 0.001% by weight or less of phosphorus and / or phosphorus-containing compounds, calculated as elements based on the total weight of the mixture.
[0026] It is preferred that the framework of the zeolitic material obtained in (B) is substantially free of phosphorus, more preferably that the zeolitic material obtained in (B) is substantially free of phosphorus and / or phosphorus-containing compounds. It is particularly preferred that the framework of the zeolitic material obtained in (B), more preferably the zeolitic material obtained in (B), contains not more than 1% by weight phosphorus, preferably not more than 0.5%, more preferably not more than 0.1%, more preferably not more than 0.05%, more preferably not more than 0.01%, more preferably not more than 0.005%, more preferably not more than 0.001%, by weight, calculated as the element based on the total weight of the zeolitic material.
[0027] It is preferred that the mixture prepared in (A) and heated in (B) is substantially free of phosphorus and / or phosphorus-containing compounds. Thus, the inventive process disclosed herein is preferably carried out in the absence of phosphorus and / or phosphorus-containing compounds. It is particularly preferred that the mixture prepared in (1) and heated in (2) contains 1% by weight or less phosphorus, preferably 0.5% by weight or less, more preferably 0.1% by weight or less, more preferably 0.05% by weight or less, more preferably 0.01% by weight or less, more preferably 0.005% by weight or less, more preferably 0.001% by weight or less, calculated as element based on the total weight of the mixture.
[0028] It is preferred that the framework of the zeolitic material obtained in (2) is substantially free of phosphorus, more preferably that the zeolitic material obtained in (2) is substantially free of phosphorus and / or phosphorus-containing compounds. It is particularly preferred that the framework of the zeolitic material obtained in (2), more preferably the zeolitic material obtained in (B), contains 1% by weight or less of phosphorus, preferably 0.5% by weight or less, more preferably 0.1% by weight or less, more preferably 0.05% by weight or less, more preferably 0.01% by weight or less, more preferably 0.005% by weight or less, more preferably 0.001% by weight or less, calculated as the element based on the total weight of the zeolitic material.
[0029] The mixture prepared according to (A) may comprise further components. It is preferred that the mixture prepared according to (A) further comprises one or more solvents, more preferably said one or more solvents comprise water, preferably distilled water, more preferably said water is included as one or more solvents in the mixture prepared according to (A), preferably distilled water.
[0030] The mixture prepared in (A) and heated in (B) is - Preferably, the composition further comprises at least one source of said OH -Preferably, the at least one source of hydroxide comprises a metal hydroxide, more preferably an alkali metal hydroxide M, more preferably sodium hydroxide and / or potassium hydroxide, more preferably sodium hydroxide, more preferably OH - At least one source of is sodium hydroxide.
[0031] The second zeolitic material having a CHA-type framework structure preferably comprises one or more zeolites having a CHA-type framework structure, the one or more zeolites having a CHA-type framework structure being selected from the group consisting of Wilhendersonite, ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R, SAPO-34, ZK-14, K-chabasite, MeAPSO-47, Phi, DAF-5, UiO-21, |Li-Na|[Al-Si-O]-CHA, (Ni(deta)2)-UT-6, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R, SAPO-34, ZK-14, K-chabasite, MeAPSO-47, Phi, DAF-5, UiO-21, |Li-Na|[Al-Si-O]-CHA, (Ni(deta)2)-UT-6, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), R, SAPO-34, ZK-14, K-chabazite, Phi, DAF-5, UiO-21, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, Linde D, Linde R, SAPO-34, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, SSZ-13 and SSZ-62, (including mixtures of two or three thereof), more preferably the second zeolitic material obtained in (B) comprises chabazite and / or SSZ-13, preferably SSZ-13, more preferably the second zeolitic material obtained in (B) is chabazite and / or SSZ-13, preferably SSZ-13.
[0032] Preferably, the one or more structure directing agents include one or more tetraalkylammonium cation-containing compounds.
[0033] When the one or more structure directing agents include one or more tetraalkylammonium cation-containing compounds, the one or more tetraalkylammonium cation-containing compounds preferably include one or more compounds selected from the group consisting of 1-adamantyltri(C1-C3)alkylammonium compounds, N,N,N-trimethyl-N-benzylammonium compounds, and mixtures of two or more thereof, more preferably from the group consisting of 1-adamantyltri(C1-C2)alkylammonium compounds, and mixtures of two or more thereof, more preferably from the group consisting of 1-adamantyltriethylammonium compounds, 1-adamantyldiethylmethylalkylammonium compounds, 1-adamantylethyl-dimethylammonium compounds, 1-adamantyltrimethyl-ammonium compounds, and mixtures of two or more thereof, more preferably the one or more tetraalkylammonium cation-containing compounds include one or more 1-adamantyltrimethylammonium compounds, and more preferably the one or more tetraalkylammonium cation-containing compounds consist of one or more 1-adamantyltrimethylammonium compounds.
[0034] Further, when the one or more structure directing agents include one or more tetraalkylammonium cation-containing compounds, the one or more tetraalkylammonium cation-containing compounds are selected from the group consisting of N,N,N-tri(C1-C2)alkyl-(C5-C6)cycloalkylammonium compounds and mixtures of two or more thereof, more preferably from the group consisting of N,N,N-tri(C1-C2)alkyl-cyclopentylammonium compounds, N,N,N-tri(C1-C2)alkyl-cyclohexylammonium compounds, and mixtures of two or more thereof, more preferably N,N,N-triethyl-cyclohexylammonium compounds, N,N- Preferably, the one or more tetraalkylammonium cation-containing compounds comprise one or more compounds selected from the group consisting of diethyl-N-methyl-cyclohexylammonium compounds, N,N-dimethyl-N-ethyl-cyclohexylammonium compounds, N,N,N-trimethyl-cyclohexylammonium compounds, and mixtures of two or more thereof; more preferably, the one or more tetraalkylammonium cation-containing compounds comprise one or more N,N,N-trimethyl-cyclohexylammonium compounds; and more preferably, the one or more tetraalkylammonium cation-containing compounds consist of one or more N,N,N-trimethyl-cyclohexylammonium compounds.
[0035] Additionally, when the one or more structure directing agents include one or more tetraalkylammonium cation-containing compounds, the one or more tetraalkylammonium cation-containing compounds may include one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + It is preferable that the compound contains R 1 , R 2 , R 3 and R is 4 each independently represents alkyl; R 3 and R 4 form a common alkyl chain.
[0036] The one or more tetraalkylammonium cation-containing compounds may contain one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + Containing compound (in the formula, R 1 , R 2 , R 3 and R is 4 each independently represents alkyl; R 3 and R 4 form a common alkyl chain), R 1 and R 2 are each independently an optionally substituted and / or optionally branched (C1-C6) alkyl, more preferably a (C1-C5) alkyl, more preferably a (C1-C4) alkyl, more preferably a (C1-C3) alkyl, more preferably an optionally substituted methyl or ethyl, more preferably R 1 and R 2 each independently represents optionally substituted methyl or ethyl, preferably unsubstituted methyl or ethyl, more preferably R 1 and R 2 independently of one another represent optionally substituted ethyl, preferably unsubstituted ethyl.
[0037] Further, the one or more tetraalkylammonium cation-containing compounds may contain one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + Containing compound (in the formula, R 1 , R 2 , R 3 and R is 4 each independently represents alkyl; R 3 and R 4 form a common alkyl chain), R 3 and R 4form a common derivatized or non-derivatized, preferably non-derivatized, alkyl chain, more preferably a common (C4-C8) alkyl chain, more preferably a common (C4-C7) alkyl chain, more preferably a common (C4-C6) alkyl chain, more preferably said common alkyl chain being a derivatized or non-derivatized, preferably non-derivatized C4 or C5 alkyl chain, more preferably a derivatized or non-derivatized, preferably non-derivatized C5 alkyl chain.
[0038] Further, the one or more tetraalkylammonium cation-containing compounds may contain one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + Containing compound (in the formula, R 1 , R 2 , R 3 and R is 4 each independently represents alkyl; R 3 and R 4 form a common alkyl chain), one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N +The compounds contained are N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylhexahydroazepinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)a and mixtures of two or more thereof, more preferably from the group consisting of N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylhexahydroazepinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpyrrolidinium compounds. , N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylhexahydroazepinium compounds, and mixtures of two or more thereof, more preferably N,N-di(C1-C3)alkyl-3,5-di(C1-C3)alkylpyrrolidinium compounds, N,N-di(C1-C3)alkyl-3,5-di(C1-C3)alkylpiperidinium compounds, N,N-di(C1-C3)alkyl-3,5-di(C1-C3)alkyl From the group consisting of hexahydroazepinium compounds, N,N-di(C1-C3)alkyl-2,6-di(C1-C3)alkylpyrrolidinium compounds, N,N-di(C1-C3)alkyl-2,6-di(C1-C3)alkylpiperidinium compounds, N,N-di(C1-C3)alkyl-2,6-di(C1-C3)alkylhexahydroazepinium compounds, and mixtures of two or more thereof, more preferably N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylpyrrolidinium compounds, N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylpiperidinium compounds, N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylhexahydroazepinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylpyrrolidinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylpiperidinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylhexahydroazepinium compounds Preferably, the compound contains one or more compounds selected from the group consisting of N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylpiperidinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylpiperidinium compounds, and mixtures of two or more thereof, more preferably one or more tetraalkylammonium cations R, 1 R 2 R 3 R 4 N + The containing compound comprises one or more N,N-dimethyl-3,5-dimethylpiperidinium compounds and / or one or more N,N-diethyl-2,6-dimethylpiperidinium compounds, preferably one or more N,N-diethyl-2,6-dimethylpiperidinium compounds, more preferably one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The containing compound comprises one or more N,N-dimethyl-3,5-dimethylpiperidinium and / or one or more N,N-diethyl-2,6-dimethylpiperidinium compounds, preferably one or more N,N-diethyl-2,6-dimethylpiperidinium compounds.
[0039] one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N +The compound is selected from the group consisting of N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylhexahydroazepinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylhexahydroazepinium compounds, and mixtures of two or more thereof. In the case where the N,N-dialkyl-2,6-dialkylpyrrolidinium compound, the N,N-dialkyl-2,6-dialkylpiperidinium compound, and / or the N,N-dialkyl-2,6-dialkylhexahydroazepinium compound are / is preferably in a cis configuration, a trans configuration, or contain a mixture of cis and trans isomers, preferably in a cis configuration, more preferably in a mixture of one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The containing compound comprises one or more ammonium compounds selected from the group consisting of N,N-di(C1-C2)alkyl-cis-2,6-di(C1-C2)alkylpiperidinium compounds, derivatized or non-derivatized, preferably non-derivatized, and mixtures of two or more thereof, more preferably one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The containing compound includes one or more N,N-diethyl-cis-2,6-dimethylpiperidinium compounds.
[0040] Furthermore, when the one or more structure directing agents comprise one or more tetraalkylammonium cation-containing compounds, the one or more tetraalkylammonium cation-containing compounds are preferably salts, more preferably one or more salts selected from the group consisting of halides, sulfates, nitrates, acetates, and mixtures of two or more thereof, more preferably one or more salts selected from the group consisting of bromides, chlorides, hydroxides, sulfates, and mixtures of two or more thereof, and more preferably the one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The containing compound is a tetraalkylammonium hydroxide and / or a tetraalkylammonium bromide, more preferably a tetraalkylammonium hydroxide.
[0041] The zeolite material contained in the seed crystal in (1) (A) preparing a mixture comprising one or more structure directing agents and a first zeolitic material comprising SiO2 and X2O3 in its framework structure, said first zeolitic material having a FAU-type framework structure, a FER-type framework structure, a TON-type framework structure, a MTT-type framework structure, a BEA-type framework structure, and / or a MFI-type framework structure, preferably a FAU-type framework structure; (B) heating the mixture obtained in (A) to obtain a second zeolitic material comprising SiO2 and X2O3 in its framework structure, said second zeolitic material having a CHA-type framework structure; In the case where the first zeolite material in the mixture prepared in (A) is obtained by a process comprising the steps of:
[0042] When the one or more structure directing agents comprise one or more tetraalkylammonium cation-containing compounds, the mixture prepared in (A) and heated in (B) preferably exhibits a molar ratio of the one or more tetraalkylammonium cations to SiO2 in the framework structure of the first zeolitic material in the range of 0.01 to 1.5, more preferably 0.03 to 1, more preferably 0.05 to 0.8, more preferably 0.08 to 0.5, more preferably 0.1 to 0.4, more preferably 0.12 to 0.35, more preferably 0.14 to 0.3, more preferably 0.16 to 0.25, more preferably 0.18 to 0.22.
[0043] Furthermore, the zeolite material contained in the seed crystal in (1) is (A) preparing a mixture comprising one or more structure directing agents and a first zeolitic material comprising SiO2 and X2O3 in its framework structure, said first zeolitic material having a FAU-type framework structure, a FER-type framework structure, a TON-type framework structure, a MTT-type framework structure, a BEA-type framework structure, and / or a MFI-type framework structure, preferably a FAU-type framework structure; (B) heating the mixture obtained in (A) to obtain a second zeolitic material comprising SiO2 and X2O3 in its framework structure, said second zeolitic material having a CHA-type framework structure; and wherein, independently of each other, the framework structure of said first zeolitic material preferably exhibits a SiO2:X2O three molar ratio in the range of 3-80, more preferably 5-50, more preferably 7-30, more preferably 9-20, more preferably 10-15, and more preferably 11-13.
[0044] Furthermore, when the zeolitic material contained in the seed crystals in (1) is obtained by a process including (A) and (B), each as disclosed herein, the mixture prepared in (A) and heated in (B) may be a mixture of OH - and the mixture further comprises at least one source of hydroxide OH relative to SiO in the framework structure of the first zeolite material. -The molar ratio of SiO2 is in the range of 0.005 to 1, more preferably 0.01 to 0.5, more preferably 0.03 to 0.3, more preferably 0.05 to 0.2, more preferably 0.07 to 0.15, more preferably 0.08 to 0.13, and more preferably 0.09 to 0.11.
[0045] Furthermore, when the zeolite material contained in the seed crystals in (1) is obtained by a method including (A) and (B), each as disclosed in the present specification, the heating in (B) is preferably carried out at a temperature in the range of 80 to 250°C, more preferably 100 to 230°C, more preferably 110 to 210°C, more preferably 120 to 200°C, more preferably 125 to 190°C, more preferably 130 to 180°C, more preferably 135 to 170°C, more preferably 140 to 160°C, more preferably 145 to 155°C.
[0046] Furthermore, when the zeolite material contained in the seed crystals in (1) is obtained by a method including (A) and (B), each as disclosed in the present specification, the heating in (B) is preferably carried out for a time in the range of 3 hours to 12 days, more preferably 6 hours to 8 days, more preferably 12 hours to 5 days, more preferably 18 hours to 4 days, more preferably 1 day to 3.5 days, and more preferably 1.5 days to 2.5 days.
[0047] Furthermore, when the zeolitic material contained in the seed crystals in (1) is obtained by a process comprising (A) and (B), each as disclosed herein, it is preferred that the heating in (B) is carried out under autogenous pressure, more preferably under solvothermal conditions, more preferably under hydrothermal conditions, and preferably the heating in (B) is carried out in a pressure vessel, preferably an autoclave.
[0048] Furthermore, when the zeolitic material contained in the seed crystals in (1) is obtained by a method including (A) and (B), each as disclosed herein, after obtaining the second zeolitic material in (B), one or more of the following steps may be performed: (B.1) isolating the zeolitic material obtained in (B), preferably by filtration; and / or (B.2) washing the zeolitic material obtained in (B) or (B.1); and / or (B.3) drying the zeolitic material obtained in any of (B), (B.1) or (B.2); and / or (B.4) calcining the zeolitic material obtained in any of (B), (B.1), (B.2) or (B.3); wherein steps (B.1) and / or (B.2) and / or (B.3) may be performed in any order, and one or more of said steps are preferably repeated one or more times.
[0049] Furthermore, when the zeolitic material contained in the seed crystals in (1) is obtained by a process comprising (A) and (B), each as disclosed herein, it is preferred that the process further comprises the step of calcining the second zeolitic material obtained in (B.4), (B).
[0050] Furthermore, when the zeolitic material contained in the seed crystals in (1) is obtained by a process comprising (A) and (B), each as disclosed herein, the mixture prepared in (A) and heated in (B) does not contain any zeolitic material other than the first zeolitic material having a FAU-type framework structure, a FER-type framework structure, a TON-type framework structure, a MTT-type framework structure, a BEA-type framework structure, and / or an MFI-type framework structure, more preferably does not contain any zeolitic material other than the first zeolitic material having a FAU-type framework structure, more preferably the mixture prepared in (A) and heated in (B) does not contain any seed crystals.
[0051] The SiO2:X2O3 molar ratio of the mixture prepared in (1) is preferably in the range of 1-150, more preferably 2-100, more preferably 5-70, more preferably 10-50, more preferably 13-30, more preferably 16-25, and even more preferably 18-22.
[0052] The mixture prepared in (1) preferably comprises one or more alkali metals M, which are preferably selected from the group consisting of Li, Na, K, and mixtures of two or more thereof, more preferably the one or more alkali metals are K and / or Na, preferably K and Na.
[0053] When the mixture prepared in (1) contains one or more alkali metals M, it is preferable that the mixture prepared in (1) contains K and Na, and the Na:K molar ratio of sodium to potassium in the mixture prepared in (1) is in the range of 0.1 to 500, more preferably 0.5 to 200, more preferably 1 to 100, more preferably 2 to 50, more preferably 3 to 20, more preferably 4 to 10, more preferably 5 to 7, and more preferably 5.5 to 6.5.
[0054] Furthermore, when the mixture prepared in (1) contains one or more alkali metals M, it is preferred that the molar ratio of M2O:SiO2 in the mixture from (1) is in the range of 0.01 to 5, more preferably 0.05 to 2, more preferably 0.1 to 1.5, more preferably 0.3 to 1.2, more preferably 0.5 to 1, and more preferably 0.6 to 0.8.
[0055] Furthermore, when the mixture prepared in (1) contains one or more alkali metals M, it is preferred that M contains Na, and the molar ratio of MO:SiO in the mixture from (1) is in the range of 0.01-5, more preferably 0.05-2, more preferably 0.1-1.5, more preferably 0.3-1, more preferably 0.4-0.5, and even more preferably 0.5-0.7.
[0056] Furthermore, when the mixture prepared in (1) contains one or more alkali metals M, it is preferred that M contains K, and the molar ratio of M2O:SiO2 in the mixture from (1) is in the range of 0.005 to 1, more preferably 0.01 to 0.5, more preferably 0.03 to 0.3, more preferably 0.05 to 0.2, more preferably 0.07 to 0.15, more preferably 0.08 to 0.13, more preferably 0.09 to 0.11.
[0057] It is preferred that the one or more sources of SiO2 comprise one or more compounds selected from the group consisting of silica, silicates, and mixtures thereof, preferably from the group consisting of fumed silica, silica hydrosol, reactive amorphous solid silica, silica gel, silicic acid, water glass, sodium metasilicate hydrate, sesquisilicates, disilicates, colloidal silica, pyrogenic silica, silicate esters, tetraalkoxysilanes, and mixtures of two or more thereof, more preferably from the group consisting of fumed silica, silica hydrosol, silica gel, silicic acid, water glass, colloidal silica, pyrogenic silica, silicate esters, tetraalkoxysilanes, and mixtures of two or more thereof, more preferably from the group consisting of fumed silica, silica gel, colloidal silica, pyrogenic silica, and mixtures of two or more thereof, more preferably from the group consisting of fumed silica, silica gel, colloidal silica, pyrogenic silica, and mixtures of two or more thereof, more preferably the one or more sources of SiO2 comprise fumed silica, more preferably the one or more sources of SiO2 are fumed silica.
[0058] Furthermore, when the zeolitic material comprised in the seed crystals in (1) is obtained by a process comprising (A) and (B), respectively, as disclosed herein, X comprised as X2O3 in the framework structure of the first zeolitic material and / or X provided as one or more sources of X2O3 in (1) are, independently of each other, selected from the group consisting of Al, B, In, Ga and mixtures of two or more thereof, where X is more preferably Al and / or B, more preferably Al.
[0059] The one or more sources of X2O3 are one or more compounds selected from the group consisting of Al2O3, Al(OH)3, aluminates, aluminum alcoholates, and mixtures of two or more thereof, more preferably from the group consisting of Al(OH)3, alkali metal aluminates, alkaline earth metal aluminates, aluminum (C1-C4) alcoholates, and mixtures of two or more thereof, more preferably from the group consisting of Al(OH)3, sodium aluminate, aluminum (C2-C3) alcoholates, and mixtures of two or more thereof, more preferably from the group consisting of Al(OH)3, sodium aluminate, aluminum (C3) alcoholates, and mixtures of two or more thereof, more preferably the one or more sources of X2O3 comprise aluminum triisopropylate, more preferably the one or more sources of X2O3 are aluminum triisopropylate.
[0060] There is no particular limitation regarding the amount of seed crystals in the mixture prepared in (1). The amount of seed crystals in the mixture prepared in (1) is preferably 0.5-35% by mass, more preferably 1-30% by mass, more preferably 5-28% by mass, more preferably 10-26% by mass, more preferably 15-24% by mass, and even more preferably 18-22% by mass, based on 100% by mass of SiO2 in one or more SiO2 sources, and preferably the seed crystals are made of the second zeolite material obtained in (B).
[0061] The mixture prepared in (1) preferably further comprises one or more solvents, said one or more solvents preferably comprising water, more preferably distilled water.
[0062] When the mixture prepared in (1) further comprises one or more solvents, it is preferred that the mixture prepared in (1) further comprises water as a solvent. It is particularly preferred that the mixture prepared in (1) further comprises water as a solvent, and that the H2O:SiO2 molar ratio of the mixture prepared in (1) is in the range of 5-250, more preferably 10-200, more preferably 30-180, more preferably 50-150, more preferably 80-120, and even more preferably 90-110.
[0063] The heating in (2) is preferably carried out under solvothermal conditions, more preferably under hydrothermal conditions.
[0064] The mixture in (2) is preferably heated at a temperature in the range of 80 to 250°C, more preferably 110 to 220°C, more preferably 130 to 200°C, more preferably 150 to 190°C, and even more preferably 160 to 180°C.
[0065] The mixture in (2) is preferably heated for 6 hours to 6 days, more preferably 12 hours to 4 days, more preferably 24 hours to 3 days, and even more preferably 1.5 to 2.5 days.
[0066] The method of the present invention may comprise further method steps. After obtaining the second zeolitic material in (2), the method comprises: (2a) isolating the zeolitic material obtained in (2), preferably by filtration; and / or (2b) washing the zeolitic material obtained in (2) or (2a); and / or (2c) drying the zeolitic material obtained in (2) or (2a) or (2b); Preferably, the method further comprises one or more steps of (2a) and / or (2b) and / or (2c), which may be carried out in any order. In this regard, it is particularly preferred that one or more of (2a), (2b) and (2c) are preferably repeated one or more times.
[0067] The method of the present invention comprises the steps of: (3) It is preferable to further include a step of subjecting the zeolitic material obtained in (2), (2a), (2b) or (2c) to an ion exchange treatment. Preferably, one or more ionic extra-framework elements contained in the zeolitic framework are H + and / or NH4 + , more preferably NH4 + is ion-exchanged against
[0068] The method of the present invention comprises the steps of: (4) It is preferable to further include a step of subjecting the zeolitic material obtained in (2), (2a), (2b), (2c) or (3) to an ion exchange treatment, and preferably, the one or more ionic extra-framework elements contained in the zeolitic framework are selected from the group consisting of Sr, Zr, Cr, Mg, Mo, Fe, Co, Ni, Cu, Zn, Ru, Rh, Pd, Ag, Os, Ir, Pt, Au, and mixtures of two or more thereof, more preferably, Sr, Cr, Mo, Fe, Co, Ni, Cu, Zn, Ag, and mixtures of two or more thereof. more preferably, the one or more metal cations are selected from the group consisting of Cr, Mg, Mo, Fe, Ni, Cu, Zn, Ag, and mixtures of two or more thereof, more preferably, the one or more metal cations comprise Cu and / or Fe, preferably comprise Cu, even more preferably, the one or more metal cations comprise Cu and / or Fe, preferably consist of Cu; The one or more ionic extraframework elements are NH4 + , H + and / or an alkali metal, preferably selected from the group consisting of Li, Na, K, Cs, and combinations of two or more thereof, more preferably the one or more ionic extra-framework elements are selected from the group consisting of NH4 + , H + , Li, Na, K, and combinations of two or more thereof, more preferably H +, Na, K, and combinations of two or more thereof, and more preferably the one or more ionic extra-framework elements are H + and even more preferably the one or more ionic extraframework elements are H + It consists of:
[0069] As outlined herein, the method of the present invention may comprise further method steps. (5) calcining the zeolitic material obtained in (2), (2a), (2b), (2c), (3), or (4); It is preferred that the composition further comprises:
[0070] If the method disclosed herein further comprises, after obtaining the second zeolitic material in (B), (B.4) and / or (5), each as disclosed herein, the calcination temperature in (B.4) and / or (5) is preferably in the range of 300 to 900°C, more preferably 400 to 700°C, more preferably 450 to 650°C, even more preferably 500 to 600°C.
[0071] Depending on the mass of the zeolitic material to be calcined, the calcination time needs to be adjusted. Thus, when the method disclosed herein further comprises (B.4) and / or (5), each as disclosed herein, after obtaining the second zeolitic material in (B), the calcination in (B.4) and / or (5) is preferably carried out for a time in the range of 0.5 to 24 hours, more preferably 1 to 15 hours, more preferably 2 to 12 hours, more preferably 2.5 to 9 hours, more preferably 3 to 7 hours, more preferably 3.5 to 6.5 hours, more preferably 4 to 6 hours, more preferably 4.5 to 5.5 hours.
[0072] When the process of the present invention further comprises one or more of (2a), (2b), (2c), (3), (4) and (5), it is preferred that the process further comprises the step of (R) subjecting the zeolitic material obtained in (2a), (2b), (2c), (3), (4) or (5) to a treatment for removing at least a portion of the X, preferably the tetrahedrally coordinated X, from the framework structure of the zeolitic material.
[0073] Preferably, the organic template-free synthesis method does not include a calcination step during or after (1), or before (2), (2a), (2b), (2c), (3), (4), (5), or (R).Thus, the method of the present invention is preferably organic template-free.
[0074] The treatment (R) to remove at least a portion of X from the framework structure of the zeolitic material comprises one or more steaming steps (S).
[0075] If the treatment (R) for removing at least a portion of X from the framework structure of the zeolitic material comprises one or more steaming steps (S), said one or more steaming steps (S) are preferably carried out at a temperature of 200-1,000°C, more preferably 300-900°C, preferably 400-800°C, preferably 500-700°C, even more preferably 550-650°C.
[0076] Furthermore, when the treatment (R) for removing at least a portion of X from the framework structure of the zeolitic material comprises one or more steaming steps (S), said one or more steaming steps (S) are preferably carried out for a period of 0.1 to 48 hours, more preferably 0.2 to 24 hours, more preferably 0.3 to 12 hours, more preferably 0.35 to 6 hours, more preferably 0.4 to 4 hours, more preferably 0.45 to 2 hours, even more preferably 0.5 to 1.5 hours.
[0077] Furthermore, when the treatment (R) for removing at least a portion of X from the framework structure of the zeolitic material comprises one or more steam treatment steps (S), said one or more steam treatment steps (S) are preferably carried out with a steam concentration of 5 to 95 vol%, preferably 10 to 90 vol%, more preferably 20 to 80 vol%, more preferably 30 to 70 vol%, more preferably 40 to 60 vol%, more preferably 45 to 55 vol%, the remaining volume being preferably an inert gas, more preferably nitrogen.
[0078] Furthermore, the present invention relates to a synthetic zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure, the zeolitic material being obtainable and / or having been obtained by the method of any one of the embodiments disclosed herein.
[0079] The present invention further relates to a synthetic zeolitic material, preferably obtainable and / or obtained by the method of any one of the embodiments disclosed herein, comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure comprising SiO2 and X2O3, and one or more zeolites having an AFT-type framework structure comprising SiO2 and X2O3, where X is a trivalent element and has a viscosity of 3,000 to 3,800 cm3 under a pressure of 1,000 Pa. -1 In the CO FT-IR spectrum of zeolite materials measured in the wavenumber range, the absorption band with the highest negative absorbance is at 3,580–3,700 cm -1 , preferably 3,600 to 3,680 cm -1 , more preferably 3,620 to 3,670 cm -1 , more preferably 3,630 to 3,660 cm -1 , more preferably 3,640 to 3,650 cm -1 The absorbance band with the highest positive absorbance is 3,350–3,560 cm -1 , preferably 3,370 to 3,540 cm -1 , more preferably 3,390 to 3,520 cm -1, more preferably 3,410 to 3,500 cm -1 , more preferably 3,430 to 3,480 cm -1 , more preferably 3,450 to 3,460 cm -1 Indicates the maximum value in a range.
[0080] Preferably, the zeolitic material comprises COE-10, more preferably the synthetic zeolitic material is COE-10.
[0081] It is preferred that the framework of the zeolitic material is substantially free of phosphorus, and preferably the zeolitic material is substantially free of phosphorus or phosphorus containing compounds. It is particularly preferred that the framework of the zeolitic material, more preferably the zeolitic material, contains 1% by weight or less of phosphorus, preferably 0.5% by weight or less, more preferably 0.1% by weight or less, more preferably 0.05% by weight or less, more preferably 0.01% by weight or less, more preferably 0.005% by weight or less, more preferably 0.001% by weight or less, calculated as the element based on the total weight of the zeolitic material.
[0082] X is preferably selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, more preferably Al and / or B, more preferably Al.
[0083] The one or more zeolites having a CHA-type framework structure comprising SiO2 and X2O3 are preferably selected from the group consisting of Wilhendersonite, ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R, SAPO-34, ZK-14, K-chabasite, MeAPSO-47, Phi, DAF-5, UiO-21, |Li-Na|[Al-Si-O]-CHA, (Ni(deta)2)-UT-6, SSZ-13 and SSZ-62, including mixtures of two or more thereof, more preferably ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R, SAPO-34, ZK-14, K-chabasite, MeAPSO-47, Phi, DAF-5, UiO-21, |Li-Na|[Al-Si-O]-CHA, (Ni(deta)2)-UT-6, SSZ-13 and SSZ-62, including mixtures of two or more thereof. R, SAPO-34, ZK-14, K-chabazite, Phi, DAF-5, UiO-21, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, Linde D, Linde R, SAPO-34, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, SSZ-13 and SSZ-62, (including mixtures of two or three thereof), more preferably the one or more zeolites having a CHA-type framework structure comprise chabazite and / or SSZ-13, preferably SSZ-13, more preferably the one or more zeolites having a CHA-type framework structure are chabazite and / or SSZ-13, preferably SSZ-13.
[0084] The SiO2:X2O3 molar ratio of the zeolite material is preferably in the range of 2 to 50, more preferably 3 to 30, more preferably 4 to 20, more preferably 5 to 15, more preferably 6 to 12, more preferably 6.5 to 9, more preferably 7 to 8, more preferably 7.2 to 7.6.
[0085] Preferably, the framework structure of the one or more zeolite intergrowth phases comprises AABBCC and AACCBB crystallographic stacking sequences of six crystallographic layers each along the crystallographic c-axis, and in the framework structure of the one or more zeolite intergrowth phases consisting of 12 layers of AABBCCAACCBB crystallographic stacking sequences, the proportion of the total number of crystallographic layers consisting of AABBCC and AACCBB crystallographic stacking sequences along the crystallographic c-axis is in the range of 10 to 90% ± 5%, preferably 20 to 80% ± 5%, more preferably 30 to 70% ± 5%, more preferably 35 to 65% ± 5%, more preferably 40 to 60% ± 5%, more preferably 44 to 56% ± 5%, more preferably 46 to 54% ± 5%, more preferably 48 to 52% ± 5%, more preferably 49 to 50% ± 5%. It is particularly preferred that the fraction of the total number of crystallographic layers consisting of AABBCC and AACCBB crystallographic stacking sequences along the crystallographic c-axis in the framework structure of one or more zeolitic intergrowth phases consisting of 12 layers of AABBCCAACCBB crystallographic stacking sequences is determined by the method described in Example 3 of the Experimental Section.
[0086] The BET surface area of the zeolite material, determined according to ISO 9277:2010, is between 200 and 850 m 2 / g, more preferably 400 to 800m 2 / g, more preferably 500 to 750m 2 / g, more preferably 600 to 700m 2 / g, and even more preferably 625 to 675 m 2 It is preferable that the range is / g.
[0087] The total pore volume of the zeolite material, determined according to ISO 15901-3:2007, is between 0.2 and 90 cm 3 / g, more preferably 0.3 to 75 cm 3 / g, more preferably 0.35 to 70 cm 3 / g, more preferably 0.4 to 66 cm 3 / g, more preferably 0.42 to 64 cm 3 / g, more preferably 0.44 to 62 cm 3 / g, more preferably 0.46 to 60 cm 3 / g, more preferably 0.48 to 58 cm 3 / g, more preferably 0.5 to 56 cm 3 / g, more preferably 0.52 to 0.54 cm 3 It is preferable that the range is / g.
[0088] The mesopore volume of the zeolitic material, determined according to ISO 15901-3:2007, is between 0.1 and 0.6 cm 3 / g, more preferably 0.15 to 0.5 cm 3 / g, more preferably 0.2 to 0.45 cm 3 / g, more preferably 0.22 to 0.4 cm 3 / g, more preferably 0.24 to 0.38 cm 3 / g, more preferably 0.26 to 0.36 cm 3 / g, more preferably 0.28 to 0.34 cm 3 / g, more preferably 0.3 to 0.32 cm 3 It is preferable that the range is / g.
[0089] The deconvoluted spectrum of temperature programmed desorption of ammonia (NH3-TPD) obtained for the zeolitic material preferably exhibits a maximum in the temperature range of 150-175°C, more preferably 152-173°C, more preferably 154-171°C, more preferably 156-169°C, more preferably 158-167°C, more preferably 160-165°C, more preferably 161-163°C, and the area of the deconvoluted peak of said maximum is 0.01-1.0 mmol / g, preferably 0.03-1.0 mmol / g. This corresponds to an amount of acidic sites in the range of 0.8 mmol / g, more preferably 0.05 to 0.6 mmol / g, more preferably 0.07 to 0.5 mmol / g, more preferably 0.09 to 0.45 mmol / g, more preferably 0.11 to 0.4 mmol / g, more preferably 0.13 to 0.35 mmol / g, more preferably 0.15 to 0.3 mmol / g, more preferably 0.17 to 0.27 mmol / g, more preferably 0.19 to 0.25 mmol / g, and more preferably 0.21 to 0.23 mmol / g.
[0090] The deconvoluted spectrum of temperature programmed desorption of ammonia (NH3-TPD) obtained for the zeolitic material preferably exhibits a maximum in the temperature range of 170 to 220°C, more preferably 175 to 215°C, more preferably 180 to 212°C, more preferably 183 to 209°C, more preferably 185 to 207°C, more preferably 187 to 205°C, more preferably 189 to 203°C, more preferably 191 to 201°C, more preferably 193 to 199°C, more preferably 195 to 197°C, and the deconvoluted spectrum of said maximum The area of the peak corresponds to the amount of acidic sites in the range of 0.01 to 0.7 mmol / g, preferably 0.05 to 0.6 mmol / g, more preferably 0.1 to 0.55 mmol / g, more preferably 0.15 to 0.5 mmol / g, more preferably 0.2 to 0.49 mmol / g, more preferably 0.25 to 0.47 mmol / g, more preferably 0.3 to 0.45 mmol / g, more preferably 0.35 to 0.43 mmol / g, more preferably 0.37 to 0.41 mmol / g, and more preferably 0.39 to 0.4 mmol / g.
[0091] The deconvoluted spectrum of temperature programmed desorption of ammonia (NH3-TPD) obtained for the zeolitic material preferably exhibits a maximum in the temperature range of 180°C to 300°C, more preferably 210°C to 290°C, more preferably 230°C to 285°C, more preferably 240°C to 280°C, more preferably 245°C to 277°C, more preferably 250°C to 275°C, more preferably 255°C to 273°C, more preferably 260°C to 271°C, more preferably 263°C to 269°C, more preferably 265°C to 267°C, and the deconvolution of said maximum The area of the ionized peak corresponds to an amount of acidic sites in the range of 0.1 to 0.7 mmol / g, preferably 0.15 to 0.68 mmol / g, more preferably 0.2 to 0.64 mmol / g, more preferably 0.25 to 0.62 mmol / g, more preferably 0.3 to 0.6 mmol / g, more preferably 0.35 to 0.58 mmol / g, more preferably 0.4 to 0.56 mmol / g, more preferably 0.45 to 0.54 mmol / g, more preferably 0.47 to 0.52 mmol / g, more preferably 0.49 to 0.5 mmol / g.
[0092] Furthermore, the present invention is directed to the use of sieves as molecular sieves for ion exchange, as adsorbents, or as adsorbents for the removal of nitrogen oxides, NO x for the selective catalytic reduction (SCR) of CO; for the storage and / or adsorption of CO; for the oxidation of NH, in particular the oxidation of NH slip in diesel systems; as catalysts and / or catalyst supports for the decomposition of NO, as additives in fluid catalytic cracking (FCC) processes, and / or as catalysts in organic conversion reactions, preferably in the conversion of alcohols to olefins, more preferably in the conversion of methanol to olefins (MTO), more preferably in the conversion of nitrogen oxides NO x For selective catalytic reduction (SCR) of nitrogen oxides NO in exhaust gases from an internal combustion engine, preferably a diesel engine or a lean-burn gasoline engine, xMore preferably, the present invention relates to the use of the zeolitic material in alcohol to olefins conversion, more preferably the use of the zeolitic material in methanol to olefins (MTO) conversion catalyst.
[0093] The unit bar (abs) is 10 5 Refers to absolute pressure in Pa.
[0094] The present invention is further described by the following series of embodiments and combinations of embodiments indicated by dependency and back reference. In particular, it should be noted that in each case where the scope of the embodiments is described in the context of a term such as "the method of any one of the embodiments 1 to 4", all the embodiments in this scope are intended to be explicitly disclosed to a person skilled in the art, i.e., the wording of this term should be understood by a person skilled in the art as being equivalent to "the method of any one of the embodiments 1, 2, 3, and 4". Furthermore, it should be explicitly noted that the following series of embodiments represents a properly structured part of the description directed to the general and preferred aspects of the present invention, rather than a series of claims determining the scope of protection.
[0095] Embodiment 1. A method for producing a zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure comprising SiO2 and X2O3, and one or more zeolites having an AFT-type framework structure comprising SiO2 and X2O3, where X is a trivalent element, the method comprising: (1) preparing a mixture comprising one or more sources of SiO2, one or more sources of X2O3, and seed crystals comprising a zeolitic material, the zeolitic material comprising SiO2 and X2O3 in its framework structure and having a CHA-type framework structure; (2) heating the mixture prepared in (1) to obtain a zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure; (R) subjecting the zeolitic material obtained in (2) to a treatment in order to remove at least a portion of the X's, preferably the tetrahedrally coordinated X's, from the framework structure of the zeolitic material; A method comprising:
[0096] Embodiment 2. The process of embodiment 1, wherein the zeolitic material obtained in (2) comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure comprises COE-10, preferably the zeolitic material obtained in (2) is COE-10.
[0097] The zeolite material contained in the seed crystals of the embodiment (1) is (A) preparing a mixture comprising one or more structure directing agents and a first zeolitic material comprising SiO2 and X2O3 in its framework structure, said first zeolitic material having a FAU-type framework structure, a FER-type framework structure, a TON-type framework structure, a MTT-type framework structure, a BEA-type framework structure, and / or a MFI-type framework structure, preferably a FAU-type framework structure; (B) heating the mixture obtained in (A) to obtain a second zeolitic material comprising SiO2 and X2O3 in its framework structure, the second zeolitic material having a CHA-type framework structure; 3. The method of embodiment 1 or 2, obtained by a process comprising:
[0098] Embodiment 4. The first zeolitic material having an FAU-type framework structure comprises one or more zeolites having an FAU-type framework structure, the one or more zeolites having an FAU-type framework structure being selected from the group consisting of Li-LSX, zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, SAPO-37, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof, preferably selected from the group consisting of zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof, The process of embodiment 3, wherein the one or more zeolites having an FAU-type framework structure are more preferably selected from the group consisting of zeolite X, zeolite Y, ZSM-20, ZSM-3, faujasite, and mixtures of two or more thereof, more preferably selected from the group consisting of zeolite X, zeolite Y, faujasite, and mixtures of two or more thereof, more preferably wherein said one or more zeolites having an FAU-type framework structure comprise zeolite X and / or zeolite Y, preferably zeolite Y, more preferably wherein said one or more zeolites having an FAU-type framework structure are zeolite X and / or zeolite Y, preferably zeolite Y.
[0099] Embodiment 5. The method of any one of embodiments 1-4, wherein the mixture prepared in (1) and heated in (2) is substantially free of organic templates.
[0100] Embodiment 6. The method of any one of embodiments 3-5, wherein the mixture prepared in (A) and heated in (B) is substantially free of phosphorus and / or phosphorus-containing compounds.
[0101] Embodiment 7. The process of any one of embodiments 3 to 6, wherein the framework of the zeolitic material obtained in (B) is substantially free of phosphorus, preferably the zeolitic material obtained in (B) is substantially free of phosphorus and / or phosphorus-containing compounds.
[0102] Embodiment 8. The method of any one of embodiments 1-7, wherein the mixture prepared in (1) and heated in (2) is substantially free of phosphorus and / or phosphorus-containing compounds.
[0103] Embodiment 9. The process of any one of embodiments 1 to 8, wherein the framework of the zeolitic material obtained in (2) is substantially free of phosphorus, preferably, the zeolitic material obtained in (2) is substantially free of phosphorus and / or phosphorus-containing compounds.
[0104] Embodiment 10. The method of any one of embodiments 3-9, wherein the mixture prepared according to (A) further comprises one or more solvents, the one or more solvents preferably comprising water, preferably distilled water, more preferably the water is included as one or more solvents in the mixture prepared according to (A), preferably distilled water.
[0105] Embodiment 11. The mixture prepared in (A) and heated in (B) is OH - wherein said OH - Preferably, the at least one source of hydroxide comprises a metal hydroxide, more preferably an alkali metal hydroxide M, more preferably sodium hydroxide and / or potassium hydroxide, more preferably sodium hydroxide, more preferably OH - 11. The method of any one of embodiments 3-10, wherein at least one source of is sodium hydroxide.
[0106] Embodiment 12. The second zeolitic material having a CHA-type framework structure comprises one or more zeolites having a CHA-type framework structure, the one or more zeolites having a CHA-type framework structure being selected from the group consisting of Wilhendersonite, ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R, SAPO-34, ZK-14, K-chabasite, MeAPSO-47, Phi, DAF-5, UiO-21, |Li-Na|[Al-Si-O]-CHA, (Ni(deta)2)-UT-6, SSZ-13 and SSZ-62, including mixtures of two or more thereof, preferably ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R, R, SAPO-34, ZK-14, K-chabazite, Phi, DAF-5, UiO-21, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, Linde D, Linde R, SAPO-34, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, SSZ-13 and SSZ-62, (including mixtures of two or more thereof); more preferably, said second zeolitic material obtained in (B) comprises chabazite and / or SSZ-13, preferably SSZ-13; more preferably, said second zeolitic material obtained in (B) is chabazite and / or SSZ-13, preferably SSZ-13.
[0107] Embodiment 13. The method of any one of embodiments 3-12, wherein the one or more structure directing agents comprise one or more tetraalkylammonium cation-containing compounds.
[0108] Embodiment 14. The method of embodiment 13, wherein the one or more tetraalkylammonium cation-containing compounds comprise one or more compounds selected from the group consisting of 1-adamantyltri(C1-C3)alkylammonium compounds, N,N,N-trimethyl-N-benzylammonium compounds, and mixtures of two or more thereof, preferably 1-adamantyltri(C1-C2)alkylammonium compounds, and mixtures of two or more thereof, more preferably 1-adamantyltriethylammonium compounds, 1-adamantyldiethylmethylalkylammonium compounds, 1-adamantylethyl-dimethylammonium compounds, 1-adamantyltrimethyl-ammonium compounds, and mixtures of two or more thereof, more preferably the one or more tetraalkylammonium cation-containing compounds comprise one or more 1-adamantyltrimethylammonium compounds, more preferably the one or more tetraalkylammonium cation-containing compounds consist of one or more 1-adamantyltrimethylammonium compounds.
[0109] Embodiment 15 The one or more tetraalkylammonium cation-containing compounds are selected from the group consisting of N,N,N-tri(C1-C2)alkyl-(C5-C6)cycloalkylammonium compounds and mixtures of two or more thereof, preferably N,N,N-tri(C1-C2)alkyl-cyclopentylammonium compounds, N,N,N-tri(C1-C2)alkyl-cyclohexylammonium compounds and mixtures of two or more thereof, more preferably N,N,N-triethyl-cyclohexylammonium compounds, N,N-diethyl-N-methyl-cyclohexylammonium compounds, N 15. The method of embodiment 13 or 14, wherein the one or more tetraalkylammonium cation-containing compounds comprise one or more compounds selected from the group consisting of N,N,N-dimethyl-N-ethyl-cyclohexylammonium compounds, N,N,N-trimethyl-cyclohexylammonium compounds, and mixtures of two or more thereof, more preferably the one or more tetraalkylammonium cation-containing compounds comprise one or more N,N,N-trimethyl-cyclohexylammonium compounds, more preferably the one or more tetraalkylammonium cation-containing compounds consist of one or more N,N,N-trimethyl-cyclohexylammonium compounds.
[0110] Embodiment 16. The one or more tetraalkylammonium cation-containing compounds include one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + Contains compounds containing R 1 , R 2 , R 3 and R is 4 each independently represents alkyl; R 3 and R 4 The method of any one of embodiments 13-15, wherein:
[0111] Embodiment 17. R 1 and R 2each independently represents an optionally substituted and / or optionally branched (C1-C6) alkyl, more preferably a (C1-C5) alkyl, more preferably a (C1-C4) alkyl, more preferably a (C1-C3) alkyl, more preferably an optionally substituted methyl or ethyl, more preferably R 1 and R 2 each independently represents optionally substituted methyl or ethyl, preferably unsubstituted methyl or ethyl, more preferably R 1 and R 2 The method of embodiment 16, wherein each independently represents optionally substituted ethyl, preferably unsubstituted ethyl.
[0112] Embodiment 18 R 3 and R 4 form a common derivatized or non-derivatized, preferably non-derivatized, alkyl chain, more preferably a common (C4-C8) alkyl chain, more preferably a common (C4-C7) alkyl chain, more preferably a common (C4-C6) alkyl chain, more preferably said common alkyl chain is a derivatized or non-derivatized, preferably non-derivatized C4 or C5 alkyl chain, more preferably a derivatized or non-derivatized, preferably non-derivatized C5 alkyl chain.
[0113] Embodiment 19. The one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N +The compounds contained are N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylhexahydroazepinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)a and mixtures of two or more thereof, preferably N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpyrrolidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-3,5-di(C1-C4)alkylhexahydroazepinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpyrrolidinium compounds, From the group consisting of N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylpiperidinium compounds, N,N-di(C1-C4)alkyl-2,6-di(C1-C4)alkylhexahydroazepinium compounds, and mixtures of two or more thereof, more preferably N,N-di(C1-C3)alkyl-3,5-di(C1-C3)alkylpyrrolidinium compounds, N,N-di(C1-C3)alkyl-3,5-di(C1-C3)alkylpiperidinium compounds, N,N-di(C1-C3)alkyl-3,5-di(C1-C3)alkylhexahydroazepinium compounds, and from the group consisting of N,N-di(C1-C3)alkyl-2,6-di(C1-C3)alkylpyrrolidinium compounds, N,N-di(C1-C3)alkyl-2,6-di(C1-C3)alkylpiperidinium compounds, N,N-di(C1-C3)alkyl-2,6-di(C1-C3)alkylhexahydroazepinium compounds, more preferably N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylpyrrolidinium compounds, N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylpiperidinium compounds, N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylhexahydroazepinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylpyrrolidinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylpiperidinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylhexahydroazepinium compounds It is preferable that the compound contains one or more compounds selected from the group consisting of N,N-di(C1-C2)alkyl-3,5-di(C1-C2)alkylpiperidinium compounds, N,N-di(C1-C2)alkyl-2,6-di(C1-C2)alkylpiperidinium compounds, and mixtures of two or more thereof, more preferably one or more compounds selected from the group consisting of the one or more tetraalkylammonium cations R, 1 R 2 R 3 R 4 N + The containing compound comprises one or more N,N-dimethyl-3,5-dimethylpiperidinium compounds and / or one or more N,N-diethyl-2,6-dimethylpiperidinium compounds, preferably one or more N,N-diethyl-2,6-dimethylpiperidinium compounds, more preferably one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The method of any one of embodiments 16 to 18, wherein the containing compound comprises one or more N,N-dimethyl-3,5-dimethylpiperidinium and / or one or more N,N-diethyl-2,6-dimethylpiperidinium compounds, preferably one or more N,N-diethyl-2,6-dimethylpiperidinium compounds.
[0114] Embodiment 20. The N,N-dialkyl-2,6-dialkylpyrrolidinium compounds, N,N-dialkyl-2,6-dialkylpiperidinium compounds, and / or N,N-dialkyl-2,6-dialkylhexahydroazepinium compounds exhibit a cis configuration, a trans configuration, or contain a mixture of cis and trans isomers, preferably the N,N-dialkyl-2,6-dialkylpyrrolidinium compounds, N,N-dialkyl-2,6-dialkylpiperidinium compounds, and / or N,N-dialkyl-2,6-dialkylhexahydroazepinium compounds exhibit a cis configuration, more preferably the one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The containing compound comprises one or more ammonium compounds selected from the group consisting of N,N-di(C1-C2)alkyl-cis-2,6-di(C1-C2)alkylpiperidinium compounds, derivatized or non-derivatized, preferably non-derivatized, and mixtures of two or more thereof, more preferably the one or more tetraalkylammonium cations R 1 R 2 R 3 R 4 N + The method of embodiment 19, wherein the containing compound comprises one or more N,N-diethyl-cis-2,6-dimethylpiperidinium compounds.
[0115] Embodiment 21. The one or more tetraalkylammonium cation-containing compounds are salts, preferably one or more salts selected from the group consisting of halides, sulfates, nitrates, acetates, and mixtures of two or more thereof, more preferably one or more salts selected from the group consisting of bromides, chlorides, hydroxides, sulfates, and mixtures of two or more thereof, more preferably one or more salts selected from the group consisting of tetraalkylammonium cations R 1 R 2 R 3 R 4 N +The method of any one of embodiments 13-20, wherein the containing compound is a tetraalkylammonium hydroxide and / or a tetraalkylammonium bromide, more preferably a tetraalkylammonium hydroxide.
[0116] Embodiment 22. The method of any one of embodiments 3 to 21, wherein the molar ratio of water to SiO2 in the framework structure of the first zeolitic material in said mixture prepared in (A) is in the range of 1 to 50, preferably 3 to 30, more preferably 5 to 25, more preferably 6 to 20, more preferably 7 to 15, more preferably 8 to 12, more preferably 9 to 11.
[0117] Embodiment 23. The method of any one of embodiments 13 to 22, wherein the mixture prepared in (A) and heated in (B) exhibits a molar ratio of the one or more tetraalkylammonium cations to SiO2 in the framework structure of the first zeolitic material in the range of 0.01 to 1.5, preferably 0.03 to 1, more preferably 0.05 to 0.8, more preferably 0.08 to 0.5, more preferably 0.1 to 0.4, more preferably 0.12 to 0.35, more preferably 0.14 to 0.3, more preferably 0.16 to 0.25, more preferably 0.18 to 0.22.
[0118] Embodiment 24. The method of any one of embodiments 3 to 23, wherein, independently of each other, the framework structure of the first zeolitic material exhibits a SiO2:X2O3 molar ratio in the range of 3 to 80, preferably 5 to 50, more preferably 7 to 30, more preferably 9 to 20, more preferably 10 to 15, and more preferably 11 to 13.
[0119] 25. The mixture prepared in (A) and heated in (B) is OH - and wherein the mixture further comprises at least one source of hydroxide OH relative to SiO in the framework structure of the first zeolite material. -The method of any one of embodiments 3 to 24, wherein the SiO2 molar ratio is in the range of 0.005 to 1, preferably 0.01 to 0.5, more preferably 0.03 to 0.3, more preferably 0.05 to 0.2, more preferably 0.07 to 0.15, more preferably 0.08 to 0.13, more preferably 0.09 to 0.11.
[0120] Embodiment 26. The method of any one of embodiments 3 to 25, wherein the heating in (B) is carried out at a temperature in the range of 80 to 250°C, preferably 100 to 230°C, more preferably 110 to 210°C, more preferably 120 to 200°C, more preferably 125 to 190°C, more preferably 130 to 180°C, more preferably 135 to 170°C, more preferably 140 to 160°C, more preferably 145 to 155°C.
[0121] Embodiment 27. The method of any one of embodiments 3 to 26, wherein the heating in (B) is carried out for a time period ranging from 3 hours to 12 days, preferably from 6 hours to 8 days, more preferably from 12 hours to 5 days, more preferably from 18 hours to 4 days, more preferably from 1 day to 3.5 days, more preferably from 1.5 days to 2.5 days.
[0122] Embodiment 28. The method of any one of embodiments 3 to 27, wherein the heating in (B) is carried out under autogenous pressure, preferably under solvothermal conditions, more preferably under hydrothermal conditions, and preferably said heating in (B) is carried out in a pressure vessel, preferably an autoclave.
[0123] Embodiment 29. After obtaining the second zeolite material in (B), one or more of the following steps: (B.1) isolating the zeolitic material obtained in (B), preferably by filtration; and / or (B.2) washing the zeolitic material obtained in (B) or (B.1); and / or (B.3) drying the zeolitic material obtained in any of (B), (B.1) or (B.2); and / or (B.4) calcining the zeolitic material obtained in any of (B), (B.1), (B.2) or (B.3); 29. The method of any one of embodiments 3 to 28, further comprising steps (B.1) and / or (B.2) and / or (B.3) which may be performed in any order, and wherein one or more of said steps are preferably repeated one or more times.
[0124] Embodiment 30. The method of any one of embodiments 3 to 29, further comprising the step of calcining the second zeolitic material obtained in (B.4), (B).
[0125] Embodiment 31. The process of any one of embodiments 3 to 30, wherein the mixture prepared in (A) and heated in (B) does not contain any zeolitic material other than a first zeolitic material having a FAU-type framework structure, a FER-type framework structure, a TON-type framework structure, a MTT-type framework structure, a BEA-type framework structure, and / or an MFI-type framework structure, preferably does not contain any zeolitic material other than a first zeolitic material having a FAU-type framework structure, more preferably the mixture prepared in (A) and heated in (B) does not contain seed crystals.
[0126] Embodiment 32. The method of any one of embodiments 1 to 31, wherein the SiO2:X2O3 molar ratio of the mixture prepared in (1) is in the range of 1 to 150, preferably 2 to 100, more preferably 5 to 70, more preferably 10 to 50, more preferably 13 to 30, more preferably 16 to 25, and even more preferably 18 to 22.
[0127] Embodiment 33. The process of any one of embodiments 1 to 32, wherein the mixture prepared in (1) comprises one or more alkali metals M, preferably selected from the group consisting of Li, Na, K, and mixtures of two or more thereof, more preferably the one or more alkali metals are K and / or Na, preferably K and Na.
[0128] Embodiment 34. The method of embodiment 33, wherein the mixture prepared in (1) contains K and Na, and the Na:K molar ratio of sodium to potassium in the mixture prepared in (1) is in the range of 0.1 to 500, preferably 0.5 to 200, more preferably 1 to 100, more preferably 2 to 50, more preferably 3 to 20, more preferably 4 to 10, more preferably 5 to 7, more preferably 5.5 to 6.5.
[0129] Embodiment 35. The process of embodiment 33 or 34, wherein the molar ratio of M2O:SiO2 in said mixture according to (1) is in the range of 0.01 to 5, preferably 0.05 to 2, more preferably 0.1 to 1.5, more preferably 0.3 to 1.2, more preferably 0.5 to 1, more preferably 0.6 to 0.8.
[0130] Embodiment 36. The method of any one of embodiments 33 to 35, wherein M comprises Na, and the molar ratio of MO:SiO in the mixture from (1) is in the range of 0.01 to 5, preferably 0.05 to 2, more preferably 0.1 to 1.5, more preferably 0.3 to 1, more preferably 0.4 to 0.5, and even more preferably 0.5 to 0.7.
[0131] Embodiment 37. The method of any one of embodiments 33 to 36, wherein M comprises K, and the molar ratio of M2O:SiO2 in the mixture from (1) is in the range of 0.005 to 1, preferably 0.01 to 0.5, more preferably 0.03 to 0.3, more preferably 0.05 to 0.2, more preferably 0.07 to 0.15, more preferably 0.08 to 0.13, more preferably 0.09 to 0.11.
[0132] Embodiment 38. The method of any one of embodiments 1 to 37, wherein the one or more sources of SiO2 comprise one or more compounds selected from the group consisting of silica, silicates, and mixtures thereof, preferably from the group consisting of fumed silica, silica hydrosol, reactive amorphous solid silica, silica gel, silicic acid, water glass, sodium metasilicate hydrate, sesquisilicates, disilicates, colloidal silica, pyrogenic silica, silicate esters, tetraalkoxysilanes, and mixtures of two or more thereof, more preferably from the group consisting of fumed silica, silica hydrosol, silica gel, silicic acid, water glass, colloidal silica, pyrogenic silica, silicate esters, tetraalkoxysilanes, and mixtures of two or more thereof, more preferably from the group consisting of fumed silica, silica gel, colloidal silica, pyrogenic silica, and mixtures of two or more thereof, more preferably from the group consisting of fumed silica, silica gel, colloidal silica, pyrogenic silica, and mixtures of two or more thereof, more preferably, the one or more sources of SiO2 comprise fumed silica, more preferably the one or more sources of SiO2 are fumed silica.
[0133] Embodiment 39. The method of any one of embodiments 3 to 38, wherein X comprised as X2O3 in the framework structure of the first zeolitic material and / or preferably provided as one or more sources of X2O3 in (1) are each independently selected from the group consisting of Al, B, In, Ga and mixtures of two or more thereof, and X is preferably Al and / or B, more preferably Al.
[0134] Embodiment 40. The method of any one of embodiments 1-39, wherein the one or more sources of X2O3 are one or more compounds selected from the group consisting of Al2O3, Al(OH)3, aluminates, aluminum alcoholates, and mixtures of two or more thereof, preferably from the group consisting of Al(OH)3, alkali metal aluminates, alkaline earth metal aluminates, aluminum (C1-C4) alcoholates, and mixtures of two or more thereof, more preferably from the group consisting of Al(OH)3, sodium aluminate, aluminum (C2-C3) alcoholates, and mixtures of two or more thereof, more preferably from the group consisting of Al(OH)3, sodium aluminate, aluminum (C3) alcoholates, and mixtures of two or more thereof, more preferably wherein the one or more sources of X2O3 comprise aluminum triisopropylate, more preferably wherein the one or more sources of X2O3 are aluminum triisopropylate.
[0135] Embodiment 41. The process of any one of embodiments 1 to 40, wherein the amount of seed crystals in the mixture prepared in (1) is 0.5-35 wt.%, preferably 1-30 wt.%, more preferably 5-28 wt.%, more preferably 10-26 wt.%, more preferably 15-24 wt.%, even more preferably 18-22 wt.%, based on 100 wt.% SiO2 in the one or more sources of SiO2, and preferably the seed crystals consist of the second zeolitic material obtained in (B).
[0136] Embodiment 42. The method of any one of embodiments 1 to 41, wherein the mixture prepared in (1) further comprises one or more solvents, and the one or more solvents preferably comprise water, more preferably distilled water.
[0137] Embodiment 43. The method of embodiment 42, wherein the mixture prepared in (1) further comprises one or more solvents, the mixture prepared in (1) further comprises water as a solvent, and the H2O:SiO2 molar ratio of the mixture prepared in (1) is in the range of 5 to 250, preferably 10 to 200, more preferably 30 to 180, more preferably 50 to 150, more preferably 80 to 120, and even more preferably 90 to 110.
[0138] Embodiment 44. The method of any one of embodiments 1 to 43, wherein the heating in (2) is carried out under solvothermal conditions, preferably hydrothermal conditions.
[0139] Embodiment 45. The method of any one of embodiments 1 to 44, wherein the heating of the mixture in (2) is carried out at a temperature in the range of 80 to 250°C, preferably 110 to 220°C, more preferably 130 to 200°C, more preferably 150 to 190°C, and even more preferably 160 to 180°C.
[0140] Embodiment 46. The method of any one of embodiments 1 to 45, wherein the heating of the mixture in (2) is carried out for a period ranging from 6 hours to 6 days, preferably from 12 hours to 4 days, more preferably from 24 hours to 3 days, and even more preferably from 1.5 to 2.5 days.
[0141] After obtaining the second zeolite material in embodiment 47 (2), the method further comprises: (2a) isolating the zeolitic material obtained in (2), preferably by filtration; and / or (2b) washing the zeolitic material obtained in (2) or (2a); and / or (2c) drying the zeolitic material obtained in (2) or (2a) or (2b); wherein steps (2a) and / or (2b) and / or (2c) can be performed in any order, and wherein one or more of said steps are preferably repeated one or more times.
[0142] Embodiment 48. (3) The method further comprises subjecting the zeolitic material obtained in (2), (2a), (2b) or (2c) to an ion exchange treatment, and preferably, the one or more ionic extra-framework elements contained in the zeolitic framework are H + and / or NH4 + , more preferably NH4 + The method of any one of the preceding embodiments, wherein the compound is ion-exchanged against
[0143] Embodiment 49. (4) The method further comprises subjecting the zeolitic material obtained in (2), (2a), (2b), (2c) or (3) to an ion exchange treatment, and preferably, the one or more ionic extra-framework elements contained in the zeolitic framework are selected from the group consisting of Sr, Zr, Cr, Mg, Mo, Fe, Co, Ni, Cu, Zn, Ru, Rh, Pd, Ag, Os, Ir, Pt, Au, and mixtures of two or more thereof, more preferably Sr, Cr, Mo, Fe, Co, Ni, Cu, Zn, Ag, and mixtures of two or more thereof, more preferably Cr, M and one or more metal cations selected from the group consisting of Mg, Mo, Fe, Ni, Cu, Zn, Ag, and mixtures of two or more thereof, more preferably the one or more metal cations comprise Cu and / or Fe, preferably comprise Cu, even more preferably the one or more metal cations consist of Cu and / or Fe, preferably consist of Cu; and one or more ionic extra-framework elements are ion-exchanged with NH4 + , H + and / or an alkali metal, the alkali metal being preferably selected from the group consisting of Li, Na, K, Cs, and combinations of two or more thereof, and more preferably the one or more ionic extra-framework elements are selected from the group consisting of NH4 + , H + , Li, Na, K, and combinations of two or more thereof, more preferably H +, Na, K, and combinations of two or more thereof, and more preferably the one or more ionic extra-framework elements are H + and even more preferably said one or more ionic extraframework elements are H + The method of any one of embodiments 1 to 48, comprising:
[0144] Embodiment 50. The process of any one of embodiments 1 to 49, further comprising the step of: (5) calcining the zeolitic material obtained in (2), (2a), (2b), (2c), (3), or (4).
[0145] Embodiment 51. The method of any one of embodiments 29 to 50, wherein the calcination temperature in (B.4) and / or (5) is in the range of 300 to 900°C, preferably 400 to 700°C, more preferably 450 to 650°C, more preferably 500 to 600°C.
[0146] Embodiment 52. The method of any one of embodiments 29 to 51, wherein the calcination in (B.4) and / or (5) is carried out for a time in the range of 0.5 to 24 hours, preferably 1 to 15 hours, more preferably 2 to 12 hours, more preferably 2.5 to 9 hours, more preferably 3 to 7 hours, more preferably 3.5 to 6.5 hours, more preferably 4 to 6 hours, more preferably 4.5 to 5.5 hours.
[0147] Embodiment 53. The process of any one of embodiments 47 to 52, further comprising the step of subjecting the zeolitic material obtained in (R) (2a), (2b), (2c), (3), (4), or (5) to a treatment to remove at least a portion of the X, preferably tetrahedrally coordinated X, from the framework structure of the zeolitic material.
[0148] Embodiment 54. The method of any one of embodiments 1 to 53, wherein the organic template-free synthesis method does not include a calcination step during or after (1) or before (2), (2a), (2b), (2c), (3), (4), (5), or (R).
[0149] Embodiment 55. The method of any one of embodiments 1 to 54, wherein the treating (R) to remove at least a portion of X from the framework structure of the zeolitic material comprises one or more steaming steps (S).
[0150] Embodiment 56. The process of embodiment 55, wherein the one or more steaming steps (S) are carried out at a temperature between 200 and 1,000°C, preferably between 300 and 900°C, preferably between 400 and 800°C, preferably between 500 and 700°C, even more preferably between 550 and 650°C.
[0151] Embodiment 57. The process of embodiment 55 or 56, wherein the one or more steam treatment steps (S) are carried out for a period of 0.1 to 48 hours, preferably 0.2 to 24 hours, more preferably 0.3 to 12 hours, more preferably 0.35 to 6 hours, more preferably 0.4 to 4 hours, more preferably 0.45 to 2 hours, and even more preferably 0.5 to 1.5 hours.
[0152] Embodiment 58. The method of any one of embodiments 55 to 57, wherein the one or more steam treatment steps (S) are carried out with a steam concentration of 5 to 95% by volume, preferably 10 to 90% by volume, more preferably 20 to 80% by volume, more preferably 30 to 70% by volume, more preferably 40 to 60% by volume, more preferably 45 to 55% by volume, the remaining volume being preferably an inert gas, more preferably nitrogen.
[0153] Embodiment 59. A synthetic zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure, the zeolitic material being obtainable and / or obtained by the method of any one of embodiments 1 to 58.
[0154] Embodiment 60. A method for producing a zeolite composition comprising one or more zeolites having a CHA-type framework structure containing SiO2 and X2O3, and one or more zeolites having an AFT-type framework structure containing SiO2 and X2O3, wherein X is a trivalent element, and the viscosity of the zeolite is 3,000 to 3,800 cm3 under a pressure of 1,000 Pa. -1 In the CO FT-IR spectrum of zeolite materials measured in the wavenumber range, the absorption band with the highest negative absorbance is at 3,580–3,700 cm -1 , preferably 3,600 to 3,680 cm -1 , more preferably 3,620 to 3,670 cm -1 , more preferably 3,630 to 3,660 cm -1 , more preferably 3,640 to 3,650 cm -1 The absorbance band with the highest positive absorbance is 3,350–3,560 cm -1 , preferably 3,370 to 3,540 cm -1 , more preferably 3,390 to 3,520 cm -1 , more preferably 3,410 to 3,500 cm -1 , more preferably 3,430 to 3,480 cm -1 , more preferably 3,450 to 3,460 cm -1 A synthetic zeolitic material obtainable and / or obtained by the process of any one of embodiments 1 to 58, the maximum value being in the range.
[0155] Embodiment 61. The zeolitic material of embodiment 59 or 60, wherein the synthetic zeolitic material comprises COE-10, preferably the synthetic zeolitic material is COE-10.
[0156] Embodiment 62. The zeolitic material of any one of embodiments 59 to 61, wherein the framework of the zeolitic material is substantially free of phosphorus, preferably the zeolitic material is substantially free of phosphorus or phosphorus-containing compounds.
[0157] Embodiment 63. The zeolitic material of any one of embodiments 59 to 62, wherein X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, and X is preferably Al and / or B, more preferably Al.
[0158] Embodiment 64. The one or more zeolites having a CHA-type framework structure comprising SiO2 and X2O3 are selected from the group consisting of Wilhendersonite, ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R, SAPO-34, ZK-14, K-chabasite, MeAPSO-47, Phi, DAF-5, UiO-21, |Li-Na|[Al-Si-O]-CHA, (Ni(deta)2)-UT-6, SSZ-13 and SSZ-62, including mixtures of two or more thereof, preferably ZYT-6, SAPO-47, Na-chabasite, chabasite, LZ-218, Linde D, Linde R 64. The zeolitic material of any one of embodiments 59 to 63, wherein the one or more zeolites having a CHA-type framework structure are selected from the group consisting of chabazite, Linde D, Linde R, SAPO-34, ZK-14, K-chabazite, Phi, DAF-5, UiO-21, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, SSZ-13 and SSZ-62, (including mixtures of two or more thereof), more preferably from the group consisting of chabazite, SSZ-13 and SSZ-62, (including mixtures of two or more thereof); more preferably, the one or more zeolites having a CHA-type framework structure comprise chabazite and / or SSZ-13, preferably SSZ-13; more preferably, the one or more zeolites having a CHA-type framework structure are chabazite and / or SSZ-13, preferably SSZ-13.
[0159] Embodiment 65. The zeolitic material of any one of embodiments 59 to 64, wherein the SiO2:X2O3 molar ratio of the zeolitic material is in the range of 2 to 50, preferably 3 to 30, more preferably 4 to 20, more preferably 5 to 15, more preferably 6 to 12, more preferably 6.5 to 9, more preferably 7 to 8, more preferably 7.2 to 7.6.
[0160] Embodiment 66. The zeolitic material of any one of embodiments 59 to 65, wherein in the framework structure of the one or more zeolitic intergrowth phases, each of which comprises 6 crystallographic layers of AABBCC and AACCBB crystallographic stacking sequences along the crystallographic c-axis and which consists of 12 layers of AABBCCAACCBB crystallographic stacking sequences, the fraction of the total number of crystallographic layers consisting of AABBCC and AACCBB crystallographic stacking sequences along the crystallographic c-axis in the framework structure of the one or more zeolitic intergrowth phases is in the range of 10 to 90% ± 5%, preferably 20 to 80% ± 5%, more preferably 30 to 70% ± 5%, more preferably 35 to 65% ± 5%, more preferably 40 to 60% ± 5%, more preferably 44 to 56% ± 5%, more preferably 46 to 54% ± 5%, more preferably 48 to 52% ± 5%, more preferably 49 to 50% ± 5%.
[0161] Embodiment 67. The zeolitic material has a BET surface area, determined according to ISO 9277:2010, of 200 to 850 m 2 / g, preferably 400 to 800m 2 / g, more preferably 500 to 750m 2 / g, more preferably 600 to 700m 2 / g, and even more preferably 625 to 675 m 2 The zeolitic material of any one of embodiments 59 to 66, wherein the zeolitic viscosity is in the range of 1 / g.
[0162] Embodiment 68. The total pore volume of the zeolite material, determined according to ISO 15901-3:2007, is between 0.2 and 90 cm 3 / g, preferably 0.3 to 75 cm 3 / g, more preferably 0.35 to 70 cm 3 / g, more preferably 0.4 to 66 cm3 / g, more preferably 0.42 to 64 cm 3 / g, more preferably 0.44 to 62 cm 3 / g, more preferably 0.46 to 60 cm 3 / g, more preferably 0.48 to 58 cm 3 / g, more preferably 0.5 to 56 cm 3 / g, more preferably 0.52 to 0.54 cm 3 The zeolitic material of any one of embodiments 59 to 67, wherein the zeolitic viscosity is in the range of 1 / g.
[0163] 69. The mesopore volume of the zeolitic material, determined according to ISO 15901-3:2007, is between 0.1 and 0.6 cm 3 / g, preferably 0.15 to 0.5 cm 3 / g, more preferably 0.2 to 0.45 cm 3 / g, more preferably 0.22 to 0.4 cm 3 / g, more preferably 0.24 to 0.38 cm 3 / g, more preferably 0.26 to 0.36 cm 3 / g, more preferably 0.28 to 0.34 cm 3 / g, more preferably 0.3 to 0.32 cm 3 The zeolitic material of any one of embodiments 59 to 68, wherein the zeolitic viscosity is in the range of 1 / g.
[0164] Embodiment 70. The deconvoluted spectrum of temperature programmed desorption of ammonia (NH3-TPD) obtained for the zeolitic material exhibits a maximum in the temperature range of 150-175°C, preferably 152-173°C, more preferably 154-171°C, more preferably 156-169°C, more preferably 158-167°C, more preferably 160-165°C, more preferably 161-163°C, and the area of the deconvoluted peak of said maximum is in the range of 0.01-1.0 mmol / g, preferably 0.03-0.8 mmol / g, more preferably 0.04-0.5 mmol / g, more preferably 0.05-0.6 mmol / g. 70. The zeolitic material of any one of embodiments 59 to 69, wherein the amount of acidic sites is in the range of 0.05 to 0.6 mmol / g, more preferably 0.07 to 0.5 mmol / g, more preferably 0.09 to 0.45 mmol / g, more preferably 0.11 to 0.4 mmol / g, more preferably 0.13 to 0.35 mmol / g, more preferably 0.15 to 0.3 mmol / g, more preferably 0.17 to 0.27 mmol / g, more preferably 0.19 to 0.25 mmol / g, more preferably 0.21 to 0.23 mmol / g.
[0165] Embodiment 71. The deconvoluted spectrum of temperature programmed desorption of ammonia (NH3-TPD) obtained for the zeolitic material exhibits a maximum in the temperature range of 170 to 220°C, preferably 175 to 215°C, more preferably 180 to 212°C, more preferably 183 to 209°C, more preferably 185 to 207°C, more preferably 187 to 205°C, more preferably 189 to 203°C, more preferably 191 to 201°C, more preferably 193 to 199°C, more preferably 195 to 197°C, and the area of the deconvoluted peak of the maximum is within the range of 0.01 to 1. 71. The zeolitic material of any one of embodiments 59 to 70, corresponding to an amount of acidic sites in the range of 0.7 mmol / g, preferably 0.05 to 0.6 mmol / g, more preferably 0.1 to 0.55 mmol / g, more preferably 0.15 to 0.5 mmol / g, more preferably 0.2 to 0.49 mmol / g, more preferably 0.25 to 0.47 mmol / g, more preferably 0.3 to 0.45 mmol / g, more preferably 0.35 to 0.43 mmol / g, more preferably 0.37 to 0.41 mmol / g, more preferably 0.39 to 0.4 mmol / g.
[0166] Embodiment 72. The deconvoluted spectrum of temperature programmed desorption of ammonia (NH3-TPD) obtained for the zeolitic material exhibits a maximum in the temperature range of 180°C to 300°C, preferably 210°C to 290°C, preferably 230°C to 285°C, more preferably 240°C to 280°C, more preferably 245°C to 277°C, more preferably 250°C to 275°C, more preferably 255°C to 273°C, more preferably 260°C to 271°C, more preferably 263°C to 269°C, more preferably 265°C to 267°C, and the area of the deconvoluted peak of said maximum is 0. 72. The zeolitic material of any one of embodiments 59 to 71, wherein the amount of acidic sites is in the range of 0.1 to 0.7 mmol / g, preferably 0.15 to 0.68 mmol / g, more preferably 0.2 to 0.64 mmol / g, more preferably 0.25 to 0.62 mmol / g, more preferably 0.3 to 0.6 mmol / g, more preferably 0.35 to 0.58 mmol / g, more preferably 0.4 to 0.56 mmol / g, more preferably 0.45 to 0.54 mmol / g, more preferably 0.47 to 0.52 mmol / g, more preferably 0.49 to 0.5 mmol / g.
[0167] Embodiment 73. As a molecular sieve for ion exchange, as an adsorbent, or as a nitrogen oxide NO x for the selective catalytic reduction (SCR) of CO; for the storage and / or adsorption of CO; for the oxidation of NH, in particular the oxidation of NH slip in diesel systems; as catalysts and / or catalyst supports for the decomposition of NO, as additives in fluid catalytic cracking (FCC) processes, and / or as catalysts in organic conversion reactions, preferably in the conversion of alcohols to olefins, more preferably in the conversion of methanol to olefins (MTO), more preferably in the conversion of nitrogen oxides NO x For selective catalytic reduction (SCR) of nitrogen oxides NO in exhaust gases from an internal combustion engine, preferably a diesel engine or a lean-burn gasoline engine, xUse of the synthetic zeolitic material of any one of embodiments 59 to 72 as a catalyst for selective catalytic reduction (SCR) of, more preferably use of the zeolitic material in alcohol to olefin conversion, more preferably use of the zeolitic material in a methanol to olefins (MTO) catalyst. [Brief description of the drawings]
[0168] [Figure 1] 1 shows reconstructed ADT data from Example 3. [Diagram 2] Figure 1 shows a comparison of experimental and simulated electron diffraction patterns for zone 0100 of Example 3. In the figure, the experimental (black) and simulated (p=0.25, shown in dark grey) intensity profiles 02l, 03l and 04l are taken along the corresponding diffraction lines indicated by dark grey rectangles. [Diagram 3] FIG. 1 shows the XRD patterns of the steamed sample obtained from Example 4 compared to the H-form of zeolitic material COE-10 obtained from Example 3. In each diffractogram, the diffraction angle 2θ (in °) is shown along the horizontal axis and the intensity is plotted along the vertical axis. [Figure 4] 1 shows nitrogen adsorption-desorption measurements performed on the steamed sample obtained from Example 4 compared to the H-form of zeolitic material COE-10 obtained from Example 3. For each isotherm, the relative pressure P / P0 is shown along the horizontal axis and the adsorption volume (in cm3 / g) is plotted along the vertical axis. [Diagram 5] 1 shows the NH3-TPD profiles obtained for the steamed sample obtained from Example 4 compared to the H-form of zeolitic material COE-10 obtained from Example 3. For each TPD, temperature (in °C) is shown along the horizontal axis and the TCD signal (in arbitrary units) is plotted along the vertical axis. [Figure 6]1 shows the results of CO FT-IR measurements obtained for the H-form of the zeolite material COE-10 obtained from Example 3. In the IR spectrum, wave numbers (in cm-1) are shown along the horizontal axis and absorbance (in arbitrary units) is plotted along the vertical axis. [Figure 7] 1 shows CO FT-IR measurements obtained for the sample from Example 4 that was steam treated at 600° C. In the IR spectrum, wavenumber (in cm-1) is shown along the horizontal axis and absorbance (in arbitrary units) is plotted along the vertical axis. [Figure 8] 1 shows the results of the MTO test obtained in Example 5 for the H-type zeolite material COE-10 obtained from Example 3. In the graph, the time flow (unit time) is shown along the horizontal axis, and the conversion is indicated by "○", as well as ethene "●", propene "■", butene "▲", C1-C4 alkanes "C", and the like.
number
number
number
number
number
number
number
number
[0169] Working Example The present invention is further illustrated by the following examples and reference examples.
[0170] X-ray diffraction measurements Powder X-ray diffraction (XRD) patterns were collected on a Rigaku UltimaIII diffractometer using CuKa radiation (40 kV, 40 mA).
[0171] Nitrogen adsorption / desorption measurements Nitrogen adsorption / desorption measurements were performed on a BEL-mini analyzer (BEL Japan). All samples were degassed at 350 °C for 3 h before the measurements.
[0172] NH3-TPD measurement Ammonia temperature-programmed desorption (NH3-TPD) profiles were recorded using a multitrack TPD instrument (Japan BEL). Typically, 25 mg of catalyst was pretreated at 873 K for 1 h with He flow (50 mL / min) and then cooled to 373 K. Before NH3 adsorption, the sample was evacuated at 373 K for 1 h. Approximately 2500 Pa of NH3 was contacted with the sample at 373 K for 30 min. Subsequently, the sample was evacuated to remove weakly adsorbed NH3 at the same temperature for 30 min. Finally, the sample was heated from 373 K to 873 K with He flow (50 mL / min) at a heating rate of 10 K / min. The desorbed NH3 was monitored using a thermal conductivity detector (TCD).
[0173] CO FT-IR measurement FTIR spectra were recorded using a Jasco FTIR4100 spectrometer equipped with a TGS detector at 4 cm -1 A resolution of 1000 nm was obtained. Powder samples (approximately 30 mg) were pelletized into a free-standing disk of 1 cm diameter that was held in a glass cell. After pumping at 500 °C for 1 h, the sample was cooled to -120 °C before acquiring a background spectrum. CO was then introduced into the cell in pulsed mode (approximately 5 Pa for the first pulse, until the total pressure in the IR cell reached approximately 1000 Pa). IR spectra were acquired after the equilibrium NO pressure was reached after each pulse of CO.
[0174] Reference Example 1: Synthesis of CHA seeds 2.31 g of Y zeolite (CBV712 from Zeolyst with SiO2:Al2O3 molar ratio of 12) was added to an aqueous solution containing 0.28 g of NaOH (97%; from Wako Chemical Co.) and 7.28 g of a 20% by weight aqueous solution of trimethyladamantylammonium hydroxide (TMAdaOH) (corresponding to 1.42 g of trimethyladamantylammonium hydroxide in solution), after which the mixture was stirred for 1 h. The molar composition of the gel obtained was 1 SiO2:0.083 Al2O3:0.1 NaOH:0.2 TMAdaOH:10 H2O. The parent gel thus prepared was crystallized in an autoclave at 150 °C for 2 days under tumbling conditions (40 rpm). The crystalline solid product, a zeolitic material with a CHA-type framework, was collected by filtration, washed with distilled water, dried at 100° C. overnight, and calcined at 600° C. for 6 hours under air.
[0175] Example 2: Synthesis of COE-10 with CHA-AFT intergrowth phase 0.817 g of aluminum triisopropylate (Al(OiPr)3 (>99.9%, Kanto Chemical) was added to an aqueous solution containing 72 g of distilled water, 0.96 g of NaOH (>99%, Wako Chemical), and 0.224 g of KOH (>85%, Wako Chemical), and then stirred for 1 h. Then, 2.4 g of fumed silica (Cab-O-Sil® M5, Cabot Corporation) was added to the mixture, which was then stirred for 1 h. The molar composition of the resulting gel was 1 SiO2:0.1 Al(OiPr)3:0.6 NaOH:0.1 KOH:100 H2O. Then, 0.48 g (20 wt % based on silica) of calcined CHA seeds from Reference Example 1 was added to the mixture. The matrix gel thus prepared was crystallized in an autoclave at 170°C under tumbling conditions (20 rpm) for 2 days. The solid crystalline product was collected by filtration, washed with distilled water, and dried overnight at 100°C in air.
[0176] 1 g of the crystallized zeolitic material was treated with 100 mL of 2.5 M NH4NO3 aqueous solution at 80° C. for 3 hours. This treatment was then repeated to obtain the ammonium form of the zeolitic material. The product is referred to herein as NH4-COE-10.
[0177] The zeolitic material NH4-COE-10 was then calcined at 500°C for 5 h under air to obtain the H-form of the zeolitic material (referred to herein as H-COE-10).
[0178] Elemental analysis of the product was performed by inductively coupled plasma atomic emission spectrometer (ICP-AES, Shimadzu ICPE-9000). The mass contents of Si and Al in the H-form of zeolite COE-10 are 36.9% and 9.6%, respectively, based on the ICP results.
[0179] Example 3: Characterization of CHA-AFT intergrowth phase COE-10 A powder sample of the H-form of the zeolite material obtained from Example 2 was dispersed in ethanol using an ultrasonic bath and sprayed onto a carbon-coated copper grid using a sonifier adapted for transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), electron dispersive X-ray spectroscopy (EDXS) and automated electron diffraction tomography (ADT) investigations. The sonifier used is described in E. Mugnaioli et al., Ultramicroscopy, 109 (2009) 758-765. TEM, EDX and ADT measurements were performed on a FEI TECNAI F30 S-TWIN transmission electron microscope equipped with a field emission gun and operated at 300 kV. TEM images and nanoelectron diffraction (NED) patterns were taken with a CCD camera (16-bit 4,096 x 4,096 pixel GATAN ULTRASCAN4000) and acquired with Gatan Digital Micrograph software. Scanning transmission electron microscope (STEM) images were collected by a FISCHIONE high-angle annular dark field (HAADF) detector and acquired by Emisspec ES Vision software. Three-dimensional electron diffraction data were collected with an automatic acquisition module developed for the FEI microscope according to the procedure described by U. Kolb et al., Ultramicroscopy, 107 (2007) 507-513. For high-tilt experiments, all acquisitions were performed with a tomography holder manufactured by FISCHIONE. A semi-parallel beam (104e) with a diameter of 200 nm was focused on the sample. - / nm 2A 10 μm condenser aperture and mild illumination settings (gun lens 8, spot size 6) were used to generate 100 nm (s). Crystal position tracking was performed in microprobe STEM mode, and NED patterns were acquired sequentially in 1° steps. Tilt series were collected over the full tilt range of 90°, but may be limited by overlap of surrounding crystals or grid edges. ADT data were collected using precession of the electron beam (precessional electron diffraction, PED) according to the procedure described by R. Vincent et al., Ultramicroscopy, 53 (1994) 271-282. PED was used to improve the quality of the integration of the reflected intensity, as described by E. Mugnaioli et al., Ultramicroscopy, 109 (2009) 758-765. PED was performed using a Digistar unit developed by NanoMEGAS SPRL. The precession angle was kept at 1.0°. The eADT software package was used to process the 3D electron diffraction data as described by U. Kolb et al., Cryst. Res. Technol., 46 (2011) 542-554. The kinematic approximation I ≒ |F was calculated by a direct method implemented in the program SIR2014 as described by M.C. Burla et al., Journal of Applied Crystallography, 48 (2015) 306-309. hkl | 2 Ab initio structure analysis was performed assuming the following: Difference Fourier mapping and least-squares refinement were also performed using the software SIR2014 as described by M.C. Burla et al., Journal of Applied Crystallography, 48 (2015) 306-309. Electron scattering coefficients were obtained from Doyle and Turner as described by P.A. Doyle et al., Acta Crystallographica Section A, 24 (1968) 390-397.
[0180] The ADT data set was collected from isolated suspended particles and reconstructed with 3D diffracted light quantities. For each particle measured, the diffracted light quantities showed the same elementary lattice with diffuse scattering along the shortest round trip direction. For example, the diffracted light quantities shown in Figure 1 yielded an elementary lattice with parameters a = 14.26 Å, b = 14.23 Å, c = 15.80 Å, α = 90.0°, β = 90.1°, γ = 119.6°. Taking into account a scale factor based on the effective camera length, the lattice determined by ADT (14.245 / 15.80 = 0.9016) is consistent with the lattice parameters of loc-512_dehyd (13.4791 / 14.8954 = 0.9049). It should be noted that this is contrary to the extinction inferred from the rhombohedral centering. The data are based on a hexagonal lattice (R sym = 0.132, Laue class -3m) and the structure was solved in space group R-3m (details are given in Table 1).
[0181] The ab initio structure solution had a final residual R of 0.0981. F The five most intense maxima in the electron density map (1.13 to 0.56 eÅ) converged to -3 ) corresponds to one silicon atom and four oxygen atoms. The following twelve weakest maxima (0.38 to 0.03 eÅ -3 ) was not taken into consideration.
[0182] [Table 1]
[0183] Modeling of sequence disorder and diffraction simulations The stacking arrangement of the six-membered rings of CHA (AABBCC...) is partially disordered, and the direction c obtained from the reconstructed diffraction data (see Fig. 1) * The probability p, shown in the correlation matrix in Table 2, correlates with the volume fraction of regular reverse twins (twins through the two folding axes) in the rhombohedral crystal structure.
[0184] [Table 2]
[0185] To obtain diffuse scattering, it must be assumed that multiple twin planes arise within the scattering region due to changes in growth direction during aperiodic crystal growth, as is the case for polycomposite twins. The changes in growth direction give rise to twin planes that contain backward complex building units, such as the framework type AFT [7], which has the AABBCCAACCBB... sequence of hexagonal rings. This type of intergrowth has a reverse stacking direction c * This causes diffuse scattering of light.
[0186] The diffuse scattering between the Bragg reflections measured by ADT was compared to the diffuse scattering calculated from the simulated disordered crystal. Using the DISCUS program, a disordered CHA superstructure based on layer building units was modeled and the simulated electron diffraction patterns were compared to experimental electron diffraction patterns as described by Y. Krysiak et al., Acta Crystallographica Section A Foundations and Advances, 74 (2018) 93-101. For the stacking module of DISCUS, a correlation matrix is used that defines a particular arrangement of layer types as a function of the stacking probability p listed in Error! Reference not found. Verweisquelle konnte nicht gefunden werden. It represents the probability of layer β (AACCBB) versus layer α (AABBCC).
[0187] An example of an integrated
[0100] zone image based on ADT data for Cu_Cry1 is shown in Fig. 2. The corresponding simulated 2D electron diffraction patterns were calculated for p = 0.0-0.5 in 0.05 steps. Qualitatively, the experimental and simulated patterns of diffuse scattering in the crystallographic zone are comparable (Fig. 2). The most intense diffuse streaks in the zone
[0100] can be observed in the 02l and 04l reflections. These diffuse streaks were considered for the quantitative disorder analysis depending on the stacking probability of the layer β. Therefore, the extracted experimental diffuse streaks were compared with the diffuse lines calculated by diffuse_compare in DISCUS. The highest agreement between the experimental and simulated diffuse lines is achieved for p = 0.25 (5), which corresponds to 62.5% of the total number of crystallographic layers consisting of αα and ββ stacking and 37.5% of the part of mixed crystallographic stacking sequences αβ and βα along the crystallographic c-axis. The latter resembles the framework structure of an intergrowth phase consisting of the AABBCCAACCBB crystallographic stacking sequence, which has three AFT and three CHA cages in the unit cell and has twice the volume compared to the CHA crystal structure. Taking this into account, the CHA / AFT cage ratio can be estimated to be 4.33 by (62.5+37.5 / 2) / 37.5 / 2.
[0188] conclusion The correlation matrix shown in the Fehler!Verweisquelle konnte nicht gefunden werden. with p=0.25 statistically results in a stacking sequence in which the fourth layer α is rotated 180° and shifted by the vector [-1 / 3,1 / 3,0] (layer β). With a 75% probability, layer α is stacked in reverse. All stacking sequences αβ or αβ result in a natural tiling t-aft that is not a well-ordered CHA structure. The volume fraction of twins varies from particle to particle over p=0.25 to 0.5. Example 4: Steam treatment of COE-10 with CHA-AFT intergrowth phase A 0.5 g sample of the NH4 form of COE-10 ("NH4-COE-10") from Example 2 was loaded into the center of a quartz tube in a tubular furnace. The sample was heated to the desired temperature (500-700°C) at a rate of 5°C / min and held for 1 hour under 50% H2O / N2 conditions. Steaming was performed throughout the heating process including temperature increase and decrease. The product thus obtained is denoted as "H-COE-10-xST", where x refers to the steaming temperature. As can be seen from the XRD and N2 adsorption results shown in Figures 3 and 4, for the steamed H-COE-10, the CHA structure remained almost intact regardless of the steaming temperature. As can be seen from Table 3 below, the pore volume of the steamed samples was 0.18-0.22 cm 3 / g.
[0189] [Table 3]
[0190] The bulk Si / Al ratio of the samples after steaming remained at about 3.7, 29 As calculated from the Si MAS NMR results, the framework Si / Al ratio increased. For example, the framework Si / Al ratios of H-COE-10 and H-COE-10-600ST were 4.3 and 6.4, respectively. These results indicate that more Al atoms were removed from the framework after steaming treatment. From the NH3-TPD results shown in Figure 5, the amount of acid gradually decreased with increasing steaming temperature. The values obtained from the deconvolution of the results shown in Figure 5 are shown in Table 4 below. Furthermore, as shown from the CO adsorption FTIR results shown in Figure 6 (H-COE-10) and Figure 7 (H-COE-10-600ST), the strong acid sites were preferentially removed after steaming treatment.
[0191] [Table 4]
[0192] Example 5: MTO Test The reaction of MTO was carried out in a fixed-bed reactor under atmospheric pressure. The pressure of methanol was set at 5 kPa. Helium was used as the carrier gas. The W / F of methanol was set at 33.7 g-cat h mol-1. The catalyst was activated in flowing He at 500 °C for 1 h before the reaction and then cooled to the reaction temperature of 350 °C. The reaction products were analyzed by online gas chromatography (GC-2014, Shimadzu) equipped with a HP-PLOT / Q capillary column and an FID detector. The selectivity of the products was calculated based on the carbon number. The conversion of methanol (MeOH) was calculated based on the peak area of the GC spectrum before and after the reaction, i.e., Conv.% = [Peak Area(MeOH initial )-Peak Area(MeOH unreacted )] / Peak Area(MeOH initial ). Product selectivity was determined by dividing the peak area of the GC spectrum by the sum of all products, i.e., Sel.% = Peak Area(each product) / Peak Area(total products). It should be noted that relative correction factors were used for oxygen-containing products (i.e., dimethyl ether (DME)) and MeOH.
[0193] The results of MTO tests performed on the H-form of the zeolitic material from Example 3 ("H-COE-10") and the steamed sample obtained from Example 4 are shown in Figures 8-11, respectively. Thus, as can be seen from the results, quite surprisingly, it was found that the flow time of the H-form of the zeolitic material from Example 3 ("H-COE-10") in MTO was up to 8 times longer when steamed. Furthermore, it was unexpectedly discovered that the selectivity for ethane and propene was reversed by steaming the catalyst, and the high selectivity for propene observed in the non-steamed sample was changed to a high selectivity for ethene in the experiments performed on the steamed sample.
[0194] List of cited prior art documents - WO2013 / 068976A1 - US2012 / 0189518A1 - US6334994B1 - WO98 / 15496A1 - WO02 / 070407A1 - WO2019 / 024909A1 - GWSkeels et al.: "Synthesis and characterization of phi-type zeolites LZ-276 and LZ-277: faulted members of the ABC-D6Rfamily of zeolites", Microporous and Mesoporous Materials 1999, vol. 30, no. 2~3, pp. 335~346; - EP3167953A1; - S. Goel et al.: "Synthesis of Zeolites via lnterzeolite Transformations without Organic Structure-Directing Agents", Chem.of Materials 2015, vol.27, no.6, pp.2056-2066; - Y. Ji et al.: "Organic-Free Synthesis of CHA-Type Zeolite Catalysts for the Methanol-to-Olefins Reaction", ACS Catalysis 2015, vol. 5, no. 7, pp. 4456-4465; - Y. Naraki et al.: "ZTS-1 and ZTS-2: Novel intergrowth zeolite with AFX / CHA structure", Microporous and Mesoporous Materials 2017, vol. 254, pp. 160-169; - "Synthesis, characterization and structure of SAP0-56, a member of the ABC double-six-ring family of materials with stacking sequence AABBCCBB" by St. Wilson et al., Microporous and Mesoporous Materials 1999, vol. 28, no. 1, pp. 125-137;
Claims
1. SiO 2 and X 2 O 3 and one or more zeolites having a CHA-type framework structure comprising SiO 2 and X 2 O 3 wherein X is a trivalent element and wherein: (1) SiO 2 one or more sources of 2 O 3 and seed crystals comprising a zeolitic material, the zeolitic material having in its framework structure SiO 2 and X 2 O 3 and having a CHA-type backbone structure; (2) heating the mixture prepared in (1) to obtain a zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure; (R) subjecting the zeolitic material obtained in (2) to a treatment for removing at least a portion of X from the framework structure of the zeolitic material; A method comprising:
2. The zeolite material contained in the seed crystals of (1) is (A) One or more structure directing agents and SiO in the framework structure 2 and X 2 O 3 and a first zeolitic material comprising: (B) SiO in its framework 2 and X 2 O 3 heating the mixture obtained in (A) to obtain a second zeolitic material comprising: The method of claim 1, obtained by a process comprising:
3. 3. The method of claim 1 or 2, wherein the mixture prepared in (1) and heated in (2) is substantially free of organic templates.
4. The framework structure of the first zeolite material is 2 O 3 X in (1) 2 O 3 3. The method of claim 2, wherein X provided as one or more sources of is independently selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof.
5. 1. A synthetic zeolitic material comprising one or more zeolitic intergrowth phases of one or more zeolites having a CHA-type framework structure and one or more zeolites having an AFT-type framework structure, The CHA-type skeleton structure is SiO 2 and X 2 O 3 and the one or more zeolites having an AFT-type framework structure are 2 and X 2 O 3 wherein X is a trivalent element; In the CO FT-IR spectrum of the zeolite material measured in the wave number range of 3,000-3,800 cm −1 under a pressure of 1,000 Pa, the absorption band with the highest negative absorbance shows a minimum in the range of 3,580-3,700 cm −1 and the absorption band with the highest positive absorbance shows a maximum in the range of 3,350-3,560 cm −1 . Zeolite material.
6. 6. The zeolitic material of claim 5, wherein X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof.
7. The SiO of the zeolite material 2 :X 2 O 3 The zeolitic material according to claim 5 or 6, wherein the molar ratio of
8. 8. The zeolitic material according to claim 5, wherein the framework structure of the one or more zeolitic intergrowth phases comprises AABBCC and AACCBB crystallographic stacking sequences of six crystallographic layers each along the crystallographic c-axis, and the fraction of the total number of crystallographic layers consisting of AABBCC and AACCBB crystallographic stacking sequences along the crystallographic c-axis in the framework structure of the one or more zeolitic intergrowth phases consisting of an AABBCCAACCBB crystallographic stacking sequence of twelve layers is in the range of 10 to 90% ± 5%.
9. The temperature programmed desorption of ammonia (NH 3 9. The zeolitic material according to claim 5, wherein the deconvoluted spectrum of the zeolitic material (TFA-TPD) shows a maximum in the temperature range of 150-175° C., the area of the deconvoluted peak of said maximum corresponding to an amount of acidic sites in the range of 0.01-1.0 mmol / g.
10. The temperature programmed desorption of ammonia (NH 3 10. The zeolitic material according to claim 5, wherein the deconvoluted spectrum of the zeolitic material (TFA-TPD) shows a maximum in the temperature range of 170-220° C., the area of the deconvoluted peak of said maximum corresponding to an amount of acidic sites in the range of 0.01-0.7 mmol / g.
11. The temperature programmed desorption of ammonia (NH 3 11. The zeolitic material according to claim 5, wherein the deconvoluted spectrum of the zeolitic material (TFA-TPD) shows a maximum in the temperature range of 180-300°C, the area of the deconvoluted peak of said maximum corresponding to an amount of acidic sites in the range of 0.1-0.7 mmol / g.
12. Use of the synthetic zeolitic material according to any one of claims 5 to 11 as a molecular sieve for ion exchange, as an adsorbent or as a catalyst and / or as a catalyst support.
Citation Information
Patent Citations
Disordered molecular sieve support for selective catalytic reduction of NOx
JP2013522011A
Stabilized microporous crystalline material, method for producing the same, and its use for selective catalytic reduction of NOx
JP2015502909A
Preparation and use of molecular sieve intergrowth of cha and aft with "sfw-GME tail"
JP2022525280A
Stabilized microporous crystalline material, the mothod of making the same, and the use for selective catalytic reduction of NOX
KR1020140107365A
Molecular sieve SSZ-112, its synthesis and use
US20190127231A1